Antenna system and antenna circuit board

By integrating a high-frequency antenna circuit board with a low-dielectric layer in the GHz band antenna system, the attenuation of high-frequency radio waves is reduced, enhancing transmission characteristics and enabling larger information exchange.

JP7657729B2Active Publication Date: 2025-04-07KURARAY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021562632
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-30
Filing Date
2020-11-30
Publication Date
2025-04-07
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

Existing antenna systems for high-frequency communications face limitations in information transmission due to attenuation of high-frequency radio waves, especially when integrated with glass layers.

Method used

The integration of a high-frequency antenna circuit board with a low-dielectric layer having a lower dielectric constant than the glass layer, allowing high-frequency radio waves to pass through and reach the antenna circuit board effectively.

Benefits of technology

This configuration enhances the transmission characteristics of the antenna system in the GHz band, enabling the exchange of larger amounts of information by reducing radio wave attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657729000014
    Figure 0007657729000014
  • Figure 0007657729000015
    Figure 0007657729000015
  • Figure 0007657729000016
    Figure 0007657729000016
Patent Text Reader

Abstract

The present invention provides an antenna system which is useful for high frequency communication. The antenna system (100) is composed of: a first glass layer (101) which transmits high frequency waves; a low dielectric constant layer (103) which has a lower dielectric constant than the first glass layer (101), while being arranged adjacent to the first glass layer (101) and transmitting high frequency waves that have entered from the first glass layer (101); and an antenna circuit board (107) which is arranged adjacent to the low dielectric constant layer (103) and receives high frequency waves that have entered from the low dielectric constant layer (103), while comprising a high frequency insulating layer (105).
Need to check novelty before this filing date? Find Prior Art

Description

Related Applications

[0001] This application claims priority to Japanese Patent Application Nos. 2019-218850 and 2020-129756, filed on December 3, 2019 and July 30, 2020, respectively, filed in Japan, the entire contents of which are incorporated herein by reference. [Technical field]

[0002] The present invention relates to an antenna system useful for radio frequency communications, and to an antenna circuit board useful for this antenna system. [Background technology]

[0003] It is known to provide antennas for transmitting and receiving car telephones and mobile phones on moving objects such as automobiles. For example, Patent Document 1 (JP Patent Publication 2007-53505A) describes that an antenna made of conductive wires provided on the window glass surface or the surface of an insulating material on the body of a moving object such as an automobile is suitable for receiving radio waves such as UHF and VHF broadcast waves of television, and for transmitting and receiving wideband radio waves such as car phones, mobile phones, personal radio, commercial radio, and PHS. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-53505 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the amount of information that can be transmitted is limited for radio waves used in UHF and VHF broadcast waves, as well as for car phones, mobile phones, personal radio, commercial radio, PHS, etc. In recent years, the amount of information transmitted has been steadily increasing, and in order to transmit large amounts of information, it is necessary to use the high-frequency GHz band.

[0006] An object of the present invention is to provide an antenna system which is integrated with a glass layer and has excellent transmission characteristics in the GHz band. Another object of the present invention is to provide an antenna circuit board that has excellent transmission characteristics in the GHz band when communicating through a glass layer. Another object of the present invention is to provide a laminate of an antenna circuit board and a low dielectric layer, which has excellent transmission characteristics in the GHz band when communicating through a glass layer. [Means for solving the problem]

[0007] In order to achieve the above-mentioned object, the inventors of the present invention considered using an antenna circuit board having high accuracy for high frequencies, and discovered a new problem in that, because the transmission distance is shorter at high frequencies, the radio waves reaching the antenna circuit board are affected by obstacles that were not affected in the conventional MHz band, and are attenuated. The inventors then discovered that by placing a low dielectric layer, which has a lower dielectric constant than glass, adjacent to glass, which transmits high frequencies, and allowing radio waves to reach the antenna circuit board through the low dielectric layer, it is possible to utilize high frequencies with high precision, which led to the completion of the present invention.

[0008] That is, the present invention can be configured in the following manner. [Aspect 1] a first glass layer that is transparent to radio frequency waves; a low dielectric layer having a dielectric constant lower than that of the first glass layer, adjacent to the first glass layer, and transmitting high frequency waves incident from the first glass layer; an antenna circuit board including a high frequency insulating layer adjacent to the low dielectric layer and receiving high frequency waves incident from the low dielectric layer; An antenna system for use at frequencies of 1 GHz or higher (preferably 2 GHz or higher, more preferably 6 GHz or higher, even more preferably 30 GHz or higher, and particularly preferably 50 GHz or higher), comprising: [Aspect 2] 2. The antenna system of claim 1, wherein the high frequency insulating layer is made of a thermoplastic liquid crystal polymer or a polyimide. [Aspect 3] The antenna system according to any one of the first to second aspects, Exchange the first glass layer has a dielectric constant εg of 5.5 to 7.5 (preferably 5.8 to 7.3, more preferably 6.0 to 7.0), and the low dielectric layer has a dielectric constant εf of 2.0 to 4.0 (preferably 2.2 to 3.5, more preferably 2.4 to 3.0), as the dielectric constants in both directions. Aspect 4 The antenna system according to any one of the first to third aspects, Exchange The antenna system has a dielectric tangent tanδg of the first glass layer of 0.05 or less (preferably 0.03 or less, more preferably 0.02 or less) and a dielectric tangent tanδf of the low dielectric layer of 0.05 or less (preferably 0.03 or less, more preferably 0.01 or less) in both directions. Aspect 5 5. The antenna system according to any one of aspects 1 to 4, wherein the low dielectric layer is composed of at least one resin selected from the group consisting of polyvinyl acetal resin, olefin-vinyl carboxylate copolymer resin, ionomer resin, and acrylic resin. Aspect 6 The antenna system according to any one of the first to fifth aspects, Exchange The antenna system, wherein the high-frequency insulating layer has a dielectric constant εp of 2.0 to 4.0 (preferably 2.2 to 3.5, and more preferably 2.4 to 3.0) in both directions. Aspect 7 The antenna system according to any one of the first to sixth aspects, Exchangethe dielectric loss tangent tan δp of the high-frequency insulating layer in both directions is 0.010 or less (preferably 0.005 or less, and more preferably 0.003 or less). Aspect 8 The antenna system according to any one of aspects 1 to 7, wherein the dielectric constant εf of the low dielectric layer and the dielectric constant εp of the high-frequency insulating layer are εf / εp=30 / 70 to 60 / 40 (preferably 35 / 65 to 60 / 40, more preferably 38 / 62 to 55 / 45). Antenna system. Aspect 9 An antenna system according to any one of aspects 1 to 8, wherein the low dielectric layer has a thickness of λ / 4×n±0.050 mm (where λ is the wavelength of the high frequency wave and n is an integer) (preferably λ / 4×n±0.030 mm, and more preferably λ / 4×n±0.025 mm). Aspect 10 The antenna system according to any one of aspects 1 to 9, wherein the first glass layer is made of at least one glass selected from soda-lime glass, borate glass, borosilicate glass, aluminosilicate glass, quartz glass, alkali-free glass, and low-alkali glass. Aspect 11 An antenna system according to any one of aspects 1 to 10, further comprising a second glass layer, and a low dielectric layer and an antenna circuit board are disposed between the first glass layer and the second glass layer. Aspect 12 12. The antenna system according to any one of the first to eleventh aspects, comprising a window pane of a vehicle or a building. Aspect 13 12. The antenna system according to any one of the first to eleventh aspects, wherein the antenna system is adapted to receive radio waves while attached to a vehicle, a building, or a civil engineering structure. Aspect 14 An antenna circuit board for use in the antenna system according to any one of the first to thirteenth aspects. Aspect 15 Aspects 1-1 3 2. A laminate including an antenna circuit board and a low dielectric layer adjacent to the antenna circuit board for use in the antenna system according to any one of the above aspects.

[0009] It should be noted that any combination of at least two elements disclosed in the claims and / or the specification and / or the drawings is included in the present invention. In particular, any combination of two or more of the claims described in the claims is included in the present invention. Effect of the Invention

[0010] According to the present invention, in an antenna system, a high-frequency antenna circuit board is provided and a glass layer is provided on the antenna circuit board via a low dielectric layer, thereby suppressing high-frequency attenuation and improving the transmission characteristics of the antenna circuit board for high frequencies, making it possible to exchange large amounts of information. [Brief description of the drawings]

[0011] The present invention will be more clearly understood from the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are merely for illustration and explanation, and should not be used to define the scope of the present invention. The scope of the present invention is defined by the accompanying claims. In the accompanying drawings, the same part numbers in multiple drawings indicate the same parts. The drawings are not necessarily drawn to scale, and are exaggerated to illustrate the principles of the present invention. [Figure 1] 1 is a schematic cross-sectional view for explaining an antenna system according to a first embodiment of the present invention. [Diagram 2] FIG. 11 is a schematic cross-sectional view for explaining an antenna system according to a second embodiment of the present invention. [Diagram 3] FIG. 11 is a schematic cross-sectional view for explaining an antenna system according to a third embodiment of the present invention. [Figure 4]FIG. 11 is a schematic cross-sectional view for explaining an antenna system according to a fourth embodiment of the present invention. [Diagram 5] FIG. 11 is a schematic cross-sectional view for explaining an antenna system according to a fifth embodiment of the present invention. [Figure 6] FIG. 13 is a schematic cross-sectional view illustrating an antenna system according to a sixth embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The antenna system of the present invention comprises at least an antenna circuit board including a first glass layer that transmits high frequency waves, a low dielectric layer that has a lower dielectric constant than the first glass layer and is adjacent to the first glass layer and transmits high frequency waves incident from the first glass layer, and a high frequency insulating layer that is adjacent to the low dielectric layer and receives the high frequency waves incident from the low dielectric layer.

[0013] The high frequency that is the target of the antenna system of the present invention may be, for example, 1 GHz or higher, preferably 2 GHz or higher, more preferably 6 GHz or higher, further preferably 30 GHz or higher, and particularly preferably 50 GHz or higher. The upper limit of the frequency is not particularly limited, but may be, for example, 400 GHz or lower, preferably 300 GHz or lower.

[0014] Hereinafter, specific embodiments of the antenna system of the present invention will be described with reference to the drawings, but the antenna system of the present invention is not limited to the exemplified embodiments.

[0015] [First embodiment] Fig. 1 is a schematic cross-sectional view for explaining a manufacturing method of an antenna system according to the first embodiment. As shown in Fig. 1, an antenna system 100 according to the first embodiment includes a first glass layer 101, a low dielectric layer 103 having a lower dielectric constant than the first glass layer 101, and an antenna circuit board 107. The first glass layer 101 and the low dielectric layer 103 have portions adjacent to each other in the thickness direction, and the low dielectric layer 103 and the antenna circuit board 107 have portions adjacent to each other in the thickness direction.

[0016] In addition, although only one antenna circuit board is provided in Fig. 1, one or more (e.g., 1 to 10) antenna circuit boards may be included in one antenna system adjacent to the low dielectric layer. When multiple antenna circuit boards are included, they may be multi-band compatible including a non-high frequency antenna circuit board (a circuit board for frequencies less than 1 GHz). This also applies to the following embodiments.

[0017] The first glass layer 101 may be, for example, a window glass. The position of the antenna circuit board within the surface of the window glass is not particularly limited, and may be disposed so that one end of the antenna circuit board 107 contacts the end of the window glass, as shown in FIG. 1, or may be disposed so that the one end of the antenna circuit board 107 (the end located at the outermost side of the antenna circuit board) is located inward from the end of the window glass (for example, about 1 to 10 cm inward). Similarly to the window glass, the antenna circuit board may be disposed on vehicle glass (front glass, side glass, rear glass).

[0018] For example, in cases where visibility is required, such as in window glass or automobile glass, it is preferable to place the antenna circuit board 107 in a location that does not obstruct visibility. 1In order to prevent rust or the like caused by water absorption from the end portion, the antenna circuit in the antenna circuit board 107 may be disposed in an end region that is 0 cm to 10 cm inward from the end portion of the first glass layer 10. 1 For example, the first glass layer 10 may be located away from the edge of the first glass layer 10. 1 The end portion may be disposed in an end region 1 cm or more inward from the end portion of the insulating layer (preferably in an area 1 cm to 10 cm inward). The same applies to the following embodiments.

[0019] 1, high frequency wave A, indicated by an arrow with one end pointing toward first glass layer 101, enters first glass layer 101 from the outside and exits to the inside. Thus, in thickness direction Z indicated by double-ended arrows, first glass layer 101 has one side as an outer surface and the other as an inner surface. Low dielectric layer 103 is adjacent to the inside of first glass layer 101 in thickness direction Z, and antenna circuit board 107 is adjacent to the inside of low dielectric layer 103 in thickness direction Z.

[0020] After being incident on the outer surface of the first glass layer 101, the high frequency wave A reaches the antenna circuit board 107 via the low dielectric layer 103 adjacent to the first glass layer 101. Then, the high frequency wave A that reaches the antenna circuit board 107 is received by the antenna circuit board 107. Note that even in the embodiments described in this specification regarding only reception, not only reception but also transmission is possible, and this is the same in all the embodiments.

[0021] The antenna circuit board 107 includes a high-frequency insulating layer (hereinafter, sometimes simply referred to as an insulating layer) 105, a circuit layer 104 disposed on one surface (outer surface in the thickness direction Z) of the insulating layer 105, and a conductor layer 106 disposed on the other surface (inner surface in the thickness direction Z) of the insulating layer 105. Although only one circuit layer is shown in FIG. 1 for simplification, the antenna circuit board 107 may be a multi-layer circuit board since the insulating layer may include an inner layer circuit not shown. Furthermore, the conductor layer 106 may have a circuit pattern as necessary, or may be a reflective metal layer. When the high frequency wave A incident on the antenna circuit board 107 is reflected by the reflective metal layer in the conductor layer 106, the utilization efficiency of the high frequency wave A in the antenna circuit board 107 can be improved.

[0022] High frequency wave A has a wavelength λ at a specified frequency, and after entering the first glass layer 101, a portion of it is reflected without reaching the antenna circuit board 107. However, by making the dielectric constant εf of the low dielectric layer 103 smaller than the dielectric constant εg of the first glass layer 101, the reflectance R of the high frequency wave A from when it enters the first glass layer 101 until it reaches the surface of the antenna circuit board 107 can be reduced, and the proportion of high frequency wave A that reaches the antenna circuit board 107 can be increased.

[0023] In the antenna system 100, in the thickness direction Z, the first glass layer 101 has a thickness dg, the low dielectric layer 103 has a thickness df on the antenna circuit board 107, and the insulating layer 105 in the antenna circuit board 107 has a thickness dp. Here, when the circuit portion (circuit layer 104) occupies less than half of the surface, the thickness df of the low dielectric layer 103 is understood to be the distance between the first glass layer 101 and the insulating layer 105 ignoring the circuit portion, but for convenience it is referred to as the thickness df of the low dielectric layer 103. The thickness df on the antenna circuit board 107 may be the thickness of a low dielectric layer disposed on the incident side of the high frequency wave A with respect to the antenna circuit board.

[0024] The thickness dg of the first glass layer 101 can be appropriately set, for example, within the range of 0.1 to 100 mm depending on the application of the object to which the first glass layer is provided, and may be, for example, about 0.5 to 20 mm (for example, 1 to 20 mm), preferably about 1 to 15 mm (for example, 3 to 13 mm), and more preferably about 1.5 to 10 mm (for example, 4 to 10 mm). For example, the first glass layer 101 may be a first glass layer of a vehicle or a first glass layer of a building, or may be a first glass layer that forms laminated glass.

[0025] The thickness dp of the insulating layer 105 in the antenna circuit board 107 can be appropriately set depending on the required antenna performance, and can be selected from a wide range of, for example, 10 μm to 2.5 mm, and may be, for example, about 0.1 to 2.5 mm, preferably about 0.3 to 2.0 mm, and more preferably about 0.3 to 1.0 mm. When the antenna circuit board is a multilayer circuit board, the thickness dp of the insulating layer indicates the total thickness of the insulating layers constituting the multilayer circuit board (or the total thickness of all the insulating layers).

[0026] 1, the low dielectric layer 103 has adhesiveness to both the first glass layer 101 and the antenna circuit board 107, and the antenna circuit board 107 is attached to the first glass layer 101 via the low dielectric layer 103. Therefore, the low dielectric layer 103 has a surface that is in close contact with the first glass layer 101, and the antenna circuit board 107 has a surface that is in close contact with the low dielectric layer 103.

[0027] The low dielectric layer 103 may have a desired size relative to the antenna circuit board 107 depending on the application. As shown in FIG. 1, the dimension of the low dielectric layer 103 in the planar direction may be the same as, smaller than, or larger than the antenna circuit board 107. When the low dielectric layer 103 is larger in the planar direction than the antenna circuit board 107, the antenna circuit board 107 may be embedded in the low dielectric layer 103. The planar direction is a planar direction normal to the thickness direction Z in FIG. 1. The dimensions of the low dielectric layer and the high frequency antenna circuit board are common to the following embodiments.

[0028] If the low dielectric layer 103 does not have adhesive properties, the first glass layer 101, the low dielectric layer 103, and the antenna circuit board 107 may be adjacent to each other using an external adhesive means as necessary. In this case, it is preferable that the adjacent surfaces between the low dielectric layer 103 and the first glass layer 101 are in close contact with each other without an air gap. Similarly, it is preferable that the adjacent surfaces between the low dielectric layer 103 and the antenna circuit board 107 are in close contact with each other without an air gap.

[0029] In the first glass layer 101, the antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0030] If necessary, a protective member for protecting the antenna circuit board 107 may be provided on the back surface (i.e., the surface opposite to the surface in contact with the low dielectric layer 103) and / or the side surface of the antenna circuit board 107. For example, as the protective member, for example, a further low dielectric layer may be provided adjacent to the antenna circuit board 107. Alternatively, as the protective member, for example, a further low dielectric layer and a second glass layer may be provided adjacent to the antenna circuit board 107 in this order. Furthermore, when the antenna system 100 is used for vehicle glass or the like, a sealant may be provided on at least a part of the edge of the first glass layer 103. These are similar to the following embodiments.

[0031] [Second embodiment] FIG. 2 is a schematic cross-sectional view for explaining a manufacturing method of an antenna system according to a second embodiment. As shown in FIG. 2, an antenna system 200 according to the second embodiment includes a first glass layer 201, a low dielectric layer 203 having a dielectric constant lower than that of the first glass layer 201, an antenna circuit board 107, and a second glass layer 202 disposed opposite to the first glass layer 201 in the thickness direction Z. The same components as those in the first embodiment are denoted by the same reference numerals, and their description will be omitted. For example, the antenna system 200 may be a double-glazed glass (or laminated glass) formed by the first glass layer 201 and the second glass layer 202, and may be a window glass or a vehicle glass (front glass, side glass, rear glass) made of the double-glazed glass, or may be in a state in which the antenna circuit board 107 is disposed inside the first glass layer 201 and the second glass layer 202 via the low dielectric layer 103.

[0032] In the second embodiment, the antenna circuit board 107 is embedded in the low dielectric layer 203, and the first glass layer 201 and the second glass layer 202 are bonded to each other by the low dielectric layer 203.

[0033] High frequency wave A has a wavelength λ at a specified frequency. After entering the first glass layer 201, a portion of the wave does not reach the antenna circuit board 107 and is reflected by a specified reflectance R. However, by making the dielectric constant εf of the low dielectric layer 203 smaller than the dielectric constant εg of the first glass layer 201, the reflectance R can be reduced and the proportion of high frequency wave A that reaches the antenna circuit board 107 can be improved.

[0034] In the antenna system 200, the first glass layer 201 has a thickness dg in the thickness direction Z, the low dielectric layer 203 has a thickness df on the antenna circuit board 107, and the insulating layer 105 in the antenna circuit board 107 has a thickness dp. Here, the thickness df of the low dielectric layer 203 is understood as the distance between the first glass layer 201 and the insulating layer 105, not the distance between the first glass layer 201 and the second glass layer 202. Note that the total thickness da of the low dielectric layer 203 means the thickness of the entire low dielectric layer, and in FIG. 2, it shows the distance between the first glass layer 201 and the second glass layer 202. These are similar in all the embodiments.

[0035] The thickness dg of the first glass layer 201 can be set appropriately depending on the use of the object to which the first glass layer is attached, and may be, for example, about 0.5 to 20 mm (e.g., 1 to 20 mm), preferably about 1 to 15 mm (e.g., 3 to 13 mm), and more preferably about 1.5 to 10 mm (e.g., 4 to 10 mm).

[0036] The thickness dg' of the second glass layer 202 can also be appropriately set depending on the use of the object to which the second glass layer 202 is attached, and may be, for example, about 0.5 to 20 mm (e.g., 1 to 20 mm), preferably about 1 to 15 mm (e.g., 3 to 13 mm), and more preferably about 1.5 to 10 mm (e.g., 4 to 10 mm).

[0037] In the first glass layer 201, the antenna circuit board 107 can be disposed in a desired location and with a desired size depending on the application.

[0038] [Third embodiment] Fig. 3 is a schematic cross-sectional view for explaining a manufacturing method of an antenna system according to the third embodiment. As shown in Fig. 3, an antenna system 300 according to the third embodiment includes a first glass layer 301, a low dielectric layer 303 having a lower dielectric constant than the first glass layer 301, an antenna circuit board 107, and a second glass layer 302. Note that the same components as those in the first embodiment are denoted by the same reference numerals, and the description thereof will be omitted. The first glass layer 301 and the low dielectric layer 303 have portions adjacent to each other in the thickness direction, and the low dielectric layer 303 and the antenna circuit board 107 have portions adjacent to each other in the thickness direction. Furthermore, the antenna circuit board 107 may be attached to the second glass layer 302 by various fastening means. For example, the antenna circuit board 107 may be attached to the second glass layer 302 via an adhesive layer 308.

[0039] In this embodiment, the second glass layer 302 may be, for example, a window glass, and the antenna circuit board 107 may be disposed on the outside of the window glass.

[0040] In the third embodiment, after the high frequency wave A enters the first glass layer 301, a portion of the high frequency wave A is reflected by a predetermined reflectance R without reaching the antenna circuit board 107. However, by making the dielectric constant εf of the low dielectric layer 303 smaller than the dielectric constant εg of the first glass layer 301, the reflectance R can be reduced and the proportion of the high frequency wave A that reaches the antenna circuit board 107 can be improved.

[0041] In the antenna system 300, in the thickness direction Z, the first glass layer 301 has a thickness dg, the low dielectric layer 303 has a thickness df, and the insulating layer 105 in the antenna circuit board 107 has a thickness dp. Here, the thickness df of the low dielectric layer 303 is understood as the distance between the first glass layer 301 and the insulating layer 305, not the distance between the first glass layer 301 and the second glass layer 302. In this embodiment, the total thickness of the low dielectric layer 303 is the same as the thickness df on the antenna circuit board 107.

[0042] The first glass layer 301 may be thin from the viewpoint of weight reduction, and the thickness dg may be, for example, about 0.5 to 7 mm, preferably about 0.7 to 5 mm, and more preferably about 0.8 to 3 mm.

[0043] The thickness dg' of the second glass layer 302 can be set appropriately depending on the use of the object to which the second glass layer 302 is attached, and may be, for example, about 0.5 to 20 mm (e.g., 1 to 20 mm), preferably about 1 to 15 mm (e.g., 3 to 13 mm), and more preferably about 1.5 to 10 mm (e.g., 4 to 10 mm).

[0044] When the adhesive layer 308 is provided, the adhesive layer 308 can be made of a known or conventional adhesive material having adhesive properties to the antenna circuit board and glass, as long as the adhesive layer 308 can adhere the antenna circuit board 107 to the second glass layer. The adhesive layer 308 may also be made of an adhesive material used for low dielectric layers. Alternatively, for simplicity, the adhesive layer 308 may be a pressure-sensitive adhesive tape such as a double-sided tape.

[0045] In the second glass layer 302, the antenna circuit board 107 can be disposed in a desired size and at a desired location depending on the application.

[0046] [Fourth embodiment] Fig. 4 is a schematic cross-sectional view for explaining a manufacturing method of an antenna system according to the fourth embodiment. As shown in Fig. 4, an antenna system 400 according to the fourth embodiment includes a first glass layer 401, a low dielectric layer 403 having a lower dielectric constant than the first glass layer 401, and an antenna circuit board 107. Note that the same components as those in the first embodiment are denoted by the same reference numerals, and the description thereof will be omitted.

[0047] The first glass layer 401 and the low dielectric layer 403 have a portion adjacent to each other in the thickness direction, and the low dielectric layer 403 and the antenna circuit board 107 have a portion adjacent to each other in the thickness direction.

[0048] In this embodiment, the adherend 409 may be of various forms as long as it can fix the antenna circuit board 107, and may be, for example, a wall of a building or a side of a vehicle. The adherend 409 may also be a flexible material such as a PEN film, a PET film, or an acrylic film.

[0049] In the fourth embodiment, after the high frequency wave A enters the first glass layer 401, a portion of the high frequency wave A is reflected by a predetermined reflectance R without reaching the antenna circuit board 107. However, by making the dielectric constant εf of the low dielectric layer 403 smaller than the dielectric constant εg of the first glass layer 401, the reflectance R can be reduced and the proportion of the high frequency wave A that reaches the antenna circuit board 107 can be improved.

[0050] In the antenna system 400, in the thickness direction Z, the first glass layer 401 has a thickness dg, the low dielectric layer 403 has a thickness df, and the insulating layer 105 in the antenna circuit board 107 has a thickness dp. Here, the thickness df of the low dielectric layer 403 is understood as the distance between the first glass layer 401 and the insulating layer 105. Note that in this embodiment, the total thickness of the low dielectric layer 403 is the same as the thickness df on the antenna circuit board 107.

[0051] First glass layer 401 may be thin from the viewpoint of weight reduction, and the thickness dg may be, for example, about 0.5 to 7 mm, preferably about 0.7 to 5 mm, and more preferably about 0.8 to 3 mm.

[0052] Furthermore, the antenna system 400 may be attached to the substrate 409 by various fastening means. For example, the antenna system 400 may be attached to the substrate 409 using fastening means 408a and 408b that surround the sides of the antenna system 400. The fastening means 408a and 408b may be separate members or may be an integrated member. The fastening means may include bolts, screws, screws, etc.

[0053] In addition to or instead of the fastening means 408a and 408b, the antenna circuit board 107 and the adherend 409 may be adhered to each other via an adhesive layer such as the adhesive layer 308 shown in FIG. 3, although not shown.

[0054] For example, the adhesive layer may be made of a known or conventional adhesive material having adhesive properties for the antenna circuit board and the adherend, so long as it can adhere the antenna circuit board 107 to the adherend 409. For example, from the viewpoint of simplicity, the adhesive layer may be a pressure-sensitive adhesive material such as double-sided tape.

[0055] On the adherend 409, the antenna circuit board 107 can be arranged in a desired location and with a desired size depending on the application.

[0056] [Fifth embodiment] Fig. 5 is a schematic cross-sectional view for explaining an antenna system according to a fifth embodiment. As shown in Fig. 5, an antenna system 500 according to the fifth embodiment includes a first glass layer 501, a first low dielectric layer 503a having a lower dielectric constant than the first glass layer 501, an antenna circuit board 107, a second low dielectric layer 503b, and a second glass layer 502 disposed opposite the first glass layer 501 in the thickness direction Z. 1 The same components as those in the embodiment 1 are denoted by the same reference numerals, and the description thereof will be omitted. The antenna system 500 may be, for example, a window glass made of laminated glass formed by a first glass layer 501 and a second glass layer 502, and may be in a state in which the antenna circuit board 107 is disposed inside the first glass layer 501 and the second glass layer 502 via a first low dielectric layer 503a and a second low dielectric layer 503b.

[0057] In the fifth embodiment, the antenna circuit board 107 is embedded at the boundary between the first low dielectric layer 503a and the second low dielectric layer 503b, and the first glass layer 501 and the second glass layer 502 are bonded together by the first low dielectric layer 503a and the second low dielectric layer 503b to form laminated glass.

[0058] High frequency wave A has a wavelength λ at a specified frequency. After entering the first glass layer 501, a portion of the wave does not reach the antenna circuit board 107 and is reflected by a specified reflectance R. However, by using the first low dielectric layer 503a to make the dielectric constant εf of the first low dielectric layer 503a smaller than the dielectric constant εg of the first glass layer 501, the reflectance R can be reduced and the proportion of high frequency wave A that reaches the antenna circuit board 107 can be improved.

[0059] In the antenna system 500, in the thickness direction Z, the first glass layer 501 has a thickness dg, the first low dielectric layer 503a has a thickness df on the antenna circuit board 107, and the insulating layer 105 in the antenna circuit board 107 has a thickness dp. Here, the thickness df of the first low dielectric layer 503a on the antenna circuit board 107 is understood as the distance between the first glass layer 501 and the insulating layer 105.

[0060] In addition, the second low dielectric layer 503b has a thickness df' below the high frequency antenna circuit board 107, and the thickness df' of the second low dielectric layer 503b below the high frequency antenna circuit board 107 occupies half or more of the surface of the conductive layer 106. 2 and the conductive layer 106. The thickness df' below the antenna circuit board 107 may be the thickness of a low dielectric layer disposed on the opposite side of the antenna circuit board from the first low dielectric layer. Furthermore, the first and second low dielectric layers are integrated, and the total thickness of the low dielectric layer is understood as the distance between the first glass layer 501 and the second glass layer 502, which is the thickness da.

[0061] The thickness dg of the first glass layer 501 can be appropriately set depending on the use of the object to which the first glass layer 501 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0062] The thickness dg' of the second glass layer 502 can also be appropriately set depending on the use of the object to which the second glass layer 502 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0063] The thickness df of the first low dielectric layer 503a and the thickness df' of the second low dielectric layer 503b may be the same as or different from each other.

[0064] In the first glass layer 501, the antenna circuit board 107 can be disposed in a desired size and at a desired location depending on the application.

[0065] [Sixth embodiment] Fig. 6 is a schematic cross-sectional view for explaining an antenna system according to a sixth embodiment. As shown in Fig. 6, an antenna system 600 according to the sixth embodiment includes a first glass layer 601, a first low dielectric layer 603a having a lower dielectric constant than the first glass layer 601, an antenna circuit board 107, a second low dielectric layer 603b, and a second glass layer 602 disposed opposite the first glass layer 601 in the thickness direction Z. 1 The same components as those in the embodiment 1 are denoted by the same reference numerals, and the description thereof will be omitted. The antenna system 600 may be, for example, a window glass made of laminated glass formed by a first glass layer 601 and a second glass layer 602, and may be in a state in which the antenna circuit board 107 is disposed inside the first glass layer 601 and the second glass layer 602 via a first low dielectric layer 603a and a second low dielectric layer 603b.

[0066] In the sixth embodiment, the antenna circuit board 107 is embedded in a thick first low dielectric layer 603a together with a thin second low dielectric layer 603b. The second low dielectric layer 603b is in contact with the first low dielectric layer 603a on a surface that is not in contact with either the antenna circuit board or the second glass layer. The first low dielectric layer 603a and the second low dielectric layer 603b together form a low dielectric layer 603, and the first glass layer 601 and the second glass layer 602 are bonded together by the low dielectric layer 603 to form a laminated glass.

[0067] High frequency wave A has a wavelength λ at a specified frequency. After entering the first glass layer 601, a portion of the wave does not reach the antenna circuit board 107 and is reflected by a specified reflectance R. However, by using the first low dielectric layer 603a to make the dielectric constant εf of the first low dielectric layer 603a smaller than the dielectric constant εg of the first glass layer 601, the reflectance R can be reduced and the proportion of high frequency wave A that reaches the antenna circuit board 107 can be improved.

[0068] In the antenna system 600, in the thickness direction Z, the first glass layer 601 has a thickness dg, the first low dielectric layer 603a has a thickness df on the antenna circuit board 107, and the insulating layer 105 in the antenna circuit board 107 has a thickness dp. Here, the thickness df of the first low dielectric layer 603a on the antenna circuit board 107 is understood as the distance between the first glass layer 601 and the insulating layer 105, since it occupies less than half of the surface of the circuit portion (circuit layer 104).

[0069] In addition, the second low dielectric layer 603b has a thickness df' below the antenna circuit board 107, and since the thickness df' of the second low dielectric layer 603b below the antenna circuit board 107 accounts for more than half of the surface of the conductive layer 106, it is understood to be the distance between the second glass layer 602 and the conductive layer 106.

[0070] The thickness dg of the first glass layer 601 can be appropriately set depending on the use of the object to which the first glass layer 601 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0071] The thickness dg' of the second glass layer 602 can also be appropriately set depending on the use of the object to which the second glass layer 602 is attached, and may be, for example, about 0.5 to 20 mm, preferably about 1 to 15 mm, and more preferably about 1.5 to 10 mm.

[0072] The antenna circuit board 107 and the second low dielectric layer 603b may be embedded in the first low dielectric layer 603a. In this case, the thickness df of the first low dielectric layer 603a above the antenna circuit board 107 may be made sufficiently thicker than the thickness df' of the second low dielectric layer 603b.

[0073] In FIG. 6, when the first low dielectric layer 603a has substantially the same thickness before and after embedding the antenna circuit board 107 and the second low dielectric layer 603b, the total thickness da of the first and second low dielectric layers may be the film thickness of the first low dielectric layer 603a.

[0074] In the first glass layer 601, the antenna circuit board 107 can be disposed in a desired size and at a desired location depending on the application.

[0075] Furthermore, the present invention also includes a laminate for use in the above-mentioned antenna system or the like, the laminate including an antenna circuit board and a low dielectric layer adjacent to the antenna circuit board. The laminate of the present invention may include an antenna circuit board and a low dielectric layer adjacent to the antenna circuit board. For example, the laminate may include a laminate in which a first low dielectric layer and an antenna circuit board are laminated in this order, and a laminate in which a first low dielectric layer, an antenna circuit board, and a second low dielectric layer are laminated in this order. The laminate may further include a third layer such as a protective layer. The laminate may be combined with an adherend such as glass to form an antenna system. For example, such a laminate may constitute a part of the antenna system described in the first to sixth embodiments above.

[0076] Each component will be described below, however, these are merely examples and various modifications may be included as long as the effects of the present invention can be achieved.

[0077] (First and second glass layers) The first and second glass layers are not particularly limited in shape as long as they can transmit high frequency waves and then allow the high frequency waves to reach the antenna circuit board through the low dielectric layer. For example, they may be planar, curved, or other planar glass.

[0078] The material of the first and second glass layers is not particularly limited as long as it is a material generally used for window glass, and may be various light-transmitting transparent or semi-transparent organic glass members (e.g., acrylic members, polycarbonate members, etc.), but from the viewpoint of weather resistance and transparency, inorganic glass members such as soda-lime glass, borate glass, borosilicate glass, aluminosilicate glass, and quartz glass are preferably used. According to classification based on alkali components, non-alkali glass and low-alkali glass are included. The content of alkali metal components (e.g., Na2O, KO, Li2O) in the above glass members is preferably 15% by weight or less, more preferably 10% by weight or less.

[0079] The method of forming these glass layers may be any suitable method according to the shape and material of the glass. Typically, the glass member is prepared by melting a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon at a temperature of 1400°C to 1600°C, forming it into a thin plate, and then cooling it. Examples of the method of forming the thin plate of the glass member include a slot downdraw method, a fusion method, and a float method. The glass formed into a predetermined shape such as a plate by these methods may be thinned or may be given an uneven shape on the surface by anti-glare treatment, if necessary. In addition, in order to increase the smoothness, it may be chemically polished with a solvent such as hydrofluoric acid.

[0080] The first and second glass layers may be, for example, vehicle glazings (eg, vehicle glazings for cars, trains, airplanes, ships, etc.) or architectural glazings.

[0081] Alternatively, a second glass layer may be combined with the first glass layer and an antenna circuit board may be disposed therebetween. The second glass layer is generally a glass member disposed opposite the first glass layer in the thickness direction, and may be made of the same material as or a different material from the first glass layer.

[0082] The first and second glass layers may include a colored region, and an antenna circuit in an antenna circuit board may be disposed in the colored region. The first and / or second glass layers may have a colored region partially (e.g., an edge region, etc.) in particular when visibility is required, such as in window glass or vehicle glass.

[0083] (Low dielectric layer) The low dielectric layer has a dielectric constant lower than that of the first glass layer and serves to allow high frequency waves incident from the first glass layer to reach the antenna circuit board. The low dielectric layer has a dielectric constant smaller than that of the first glass layer when compared at the same frequency. It is preferable that the dielectric constant εf of the low dielectric layer is within the range of the following formula (I) relative to the dielectric constant εg of the first glass layer.

[0084]

number

[0085] As a specific value, for example, at a frequency of 28 GHz, relative to the dielectric constant εg of the first glass layer, the dielectric constant εf of the low dielectric layer may be, for example, εg-5 to εg-0.1, preferably εg-4.5 to εg-0.5, and more preferably εg-4 to εg-1.5.

[0086] The dielectric properties (dielectric constant and dielectric loss tangent) can be measured at 28 GHz (25°C) using a Fabry-Perot resonator (Model No. DPS03) manufactured by Keycom Corporation in accordance with JIS R 1660-2. Exchange It is possible to perform measurements with extremely high accuracy in both directions (X and Y directions), and even objects with low tan δ can be measured with high accuracy.

[0087] In one embodiment, for example, at a frequency of 28 GHz, the dielectric constant εg of the first glass layer may be 5.5 to 7.5, preferably 5.8 to 7.3, and more preferably 6.0 to 7.0, and the dielectric constant εf of the low dielectric layer may be, for example, 2.0 to 4.0, preferably 2.2 to 3.5, and more preferably 2.4 to 3.0.

[0088] In one embodiment, for example, at a frequency of 28 GHz, the dielectric tangent tanδg of the first glass layer may be 0.05 or less, preferably 0.03 or less, and more preferably 0.02 or less, and the dielectric tangent tanδf of the low dielectric layer may be, for example, 0.05 or less, preferably 0.03 or less, and more preferably 0.01 or less.

[0089] In one embodiment, the thickness (df: unit: mm) of the low dielectric layer may be in the range of λ / 4×n-0.050 to λ / 4×n+0.050, preferably in the range of λ / 4×n-0.030 to λ / 4×n+0.030, more preferably in the range of λ / 4×n-0.025 to λ / 4×n+0.025, and particularly preferably in the range of λ / 4×n-0.010 to λ / 4×n+0.010, where n is an integer (e.g., an integer of 1 to 10).

[0090] In one embodiment, the thickness (df: unit mm) of the low dielectric layer can be appropriately changed depending on the wavelength (λ) of the high frequency wave and the dielectric constant εf of the low dielectric layer, and is preferably in a range satisfying any one of the following formulae (II) to (II''), where n is an integer (for example, an integer from 1 to 10).

[0091]

number

[0092] More preferably, the range may satisfy the following formula (II').

number

[0093] More preferably, the range may satisfy the following formula (II'').

number

[0094] In one embodiment, the thickness (df: unit: mm) of the low dielectric layer on the antenna circuit board can be appropriately changed depending on the wavelength (λ) of the high frequency wave and the dielectric constant of the low dielectric layer, and is preferably in a range that satisfies any one of the following formulae (III) to (III''), where n is an integer (for example, an integer from 1 to 10).

[0095]

number

[0096] More preferably, the range may satisfy the following formula (III').

number

[0097] More preferably, the range may satisfy the following formula (III'').

number

[0098] In one embodiment, the thickness df of the low dielectric layer can be selected from a wide range of about 1 μm to 20.0 mm, and from the viewpoint of suppressing reflectance, may be, for example, about 0.1 to 20.0 mm, preferably about 0.1 to 10.0 mm, and more preferably about 0.15 to 2.0 mm.

[0099] In addition, the thickness df of the low dielectric layer may be in the thick range when used in laminated glass, and in that case, the thickness df of the low dielectric layer may be, for example, more than 0.37 mm, preferably 0.50 mm or more, and more preferably 0.75 mm or more, and is preferably 2.5 mm or less, more preferably 2.28 mm or less, even more preferably 1.6 mm or less, and even more preferably 0.85 mm or less.

[0100] On the other hand, depending on the application, the low dielectric layer may be thin, for example, the thickness df of the low dielectric layer may be, for example, 370 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, particularly preferably 60 μm or less, especially more preferably less than 50 μm, especially more preferably 45 μm or less, and most preferably 40 μm or less. In addition, it may be preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and even more preferably 20 μm or more.

[0101] When a first low dielectric layer and a second low dielectric layer are adjacent to each other on both sides of the antenna circuit board, the thickness df of the first low dielectric layer and the thickness df' of the second low dielectric layer may both be in the thick range, or both in the thin range, or one may be thick and the other in the thin range.

[0102] In one embodiment, when a first low dielectric layer and a second low dielectric layer are adjacent to each other on both sides of the antenna circuit board, the thickness and size in the planar direction of each low dielectric layer may be the same or different depending on the embodiment and use of the antenna system. When one low dielectric layer is made extremely thin compared to the other, for example, the thickness ratio (df / df', where df>df') between the thick low dielectric layer and the thin low dielectric layer may be 3 / 1 to 30 / 1, preferably 4 / 1 to 20 / 1. When such a thickness ratio is present, for example, when forming a laminated glass in which an antenna circuit board is disposed inside a thick low dielectric layer, it is possible to produce the laminated glass without hollowing out the interlayer for laminated glass to fill the step or using a spacer to fill the step.

[0103] This can be set appropriately depending on the application and the thickness of the circuit board. For example, when the first and second low dielectric layers are integrated, the total thickness da of the low dielectric layers may be about 0.1 to 40 mm, preferably about 0.5 to 30 mm, and more preferably about 1.0 to 25 mm.

[0104] The low dielectric layer is not particularly limited as long as it has a predetermined dielectric constant and can be adjacent to the first glass layer, and may be formed, for example, from a thermoplastic resin or a thermosetting resin having a predetermined dielectric constant. Here, adjacent means close contact on the adjacent surfaces of the objects, or close to a range where the incidence rate of high frequency waves is kept at the same level (for example, within a range of about ±10% of the incidence rate when they are close to each other) compared to the case of close contact.

[0105] In order to easily bond the interface between the first glass layer and the low dielectric layer, and the interface between the low dielectric layer and the antenna circuit board, it is preferable that the low dielectric layer itself is an adhesive low dielectric layer having adhesiveness. The low dielectric layer may have adhesiveness to the first glass layer or to the antenna circuit board, and is preferably adhesive to both.

[0106] When the low dielectric layer has thermal adhesiveness, the low dielectric layer material may be melted to fuse the antenna circuit board and the first glass via the low dielectric layer material. Alternatively, when a solution in which the low dielectric layer material is dissolved in a solvent has adhesiveness, the low dielectric layer material solution may be applied to the joining surfaces of the first glass and / or the antenna circuit board to bond the antenna circuit board and the first glass via the low dielectric layer material. In addition, the fusion or adhesion (hereinafter referred to as fusion, etc.) is preferably carried out under degassing and / or reduced pressure in order to prevent air from being mixed in. Degassing may be carried out by physically pushing air out from the bonding interface. The fusion or the like may be performed by performing preliminary fusion or the like to position the antenna circuit board, and then fusion or the like between the antenna circuit board and the first glass under degassing and / or reduced pressure.

[0107] Examples of the adhesive low dielectric layer include polyvinyl acetal resin, olefin-vinyl carboxylate copolymer resin, ionomer resin, acrylic resin, etc., which have good affinity with glass materials. When the adhesive low dielectric layer can be bonded by heat and pressure bonding, it is possible to suppress the occurrence of circuit breakage and deformation during the bonding, and even if the glass substrate is a curved glass such as an automobile windshield, it is possible to follow and suppress foaming and peeling. Furthermore, when forming an antenna system as a laminated glass in which a high frequency antenna circuit board is embedded between the glass substrates, lamination can be performed under general manufacturing conditions for laminated glass, so that extra steps can be omitted.

[0108] (Polyvinyl acetal resin) Examples of the polyvinyl acetal resin include polyvinyl acetal resins produced by acetalizing a vinyl alcohol resin such as polyvinyl alcohol or a vinyl alcohol copolymer. When the low dielectric layer contains a polyvinyl acetal resin, it may contain one type of polyvinyl acetal resin, or may contain two or more polyvinyl acetal resins that are different in at least one of the viscosity average polymerization degree, acetalization degree, acetyl group amount, hydroxyl group amount, ethylene content, molecular weight of aldehyde used for acetalization, and chain length. When the polyvinyl acetal resin contains two or more different polyvinyl acetal resins, it is preferable from the viewpoint of ease of melt molding to be a mixture of two or more polyvinyl acetal resins that are different in at least one of the viscosity average polymerization degree, acetalization degree, acetyl group amount, and hydroxyl group amount.

[0109] The polyvinyl acetal resin used in the present invention can be obtained by a known or conventional method, for example, an acetalization reaction is carried out by adding an aldehyde (or a keto compound) and an acid catalyst to an aqueous solution of polyvinyl alcohol or a vinyl alcohol copolymer. The reaction solution is then filtered as necessary, neutralized by adding a neutralizing agent such as an alkali, and the resin is filtered, washed with water and dried to obtain a polyvinyl acetal resin.

[0110] Polyvinyl alcohol can be obtained by saponifying a polyvinyl ester obtained by polymerizing a vinyl ester compound, and a vinyl alcohol copolymer can be obtained by saponifying a copolymer of a vinyl ester compound and another monomer.

[0111] Examples of vinyl ester compounds include vinyl acetate, 1-propenyl acetate, 1-methylvinyl acetate, 1-butenyl acetate, 2-methyl-1-propenyl acetate, vinyl propionate, vinyl butanoate, vinyl pivalate, vinyl versatate, vinyl pentanoate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl dodecanoate, vinyl hexadecanoate, vinyl octadecanoate, and other aliphatic vinyl carboxylates, and vinyl aromatic vinyl carboxylates, such as vinyl benzoate. These vinyl ester compounds can be used alone or in combination. Among these vinyl ester compounds, vinyl acetate is preferred from the viewpoint of productivity.

[0112] Examples of other monomers include α-olefins such as ethylene, propylene, n-butene, and isobutylene; acrylic acid and its salts; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid and its salts; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, Methacrylic acid esters such as i-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide; N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts or its quaternary salts, N-methylolacrylamide, methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid and its salts, methacrylamidepropyldimethylamine and its salts or its quaternary salts, N-methylolmethacrylamide and its derivatives; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; nitriles such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid and their salts, esters, or anhydrides; and vinyl silyl compounds such as vinyltrimethoxysilane. The other monomers can be used alone or in combination of two or more thereof, and among these, ethylene is preferred as the other monomer.

[0113] The acid catalyst used in the acetalization reaction is not particularly limited, and any of organic and inorganic acids can be used, such as acetic acid, paratoluenesulfonic acid, nitric acid, sulfuric acid, hydrochloric acid, etc. Among them, hydrochloric acid, sulfuric acid, and nitric acid are preferred from the viewpoints of acid strength and ease of removal during washing.

[0114] The aldehyde (or keto compound) used in the production of the polyvinyl acetal resin is preferably linear, branched or cyclic having 1 to 10 carbon atoms, more preferably linear or branched. This results in a corresponding linear or branched acetal side chain. The polyvinyl acetal resin used in the present invention may be obtained by acetalizing polyvinyl alcohol or a vinyl alcohol copolymer with a mixture of a plurality of aldehydes (or keto compounds). The polyvinyl alcohol or the vinyl alcohol copolymer may be composed of only one of them, or may be a mixture of polyvinyl alcohol and a vinyl alcohol copolymer.

[0115] Examples of the aldehyde include aliphatic, aromatic, and alicyclic aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, n-butyl aldehyde, isobutyl aldehyde, valeraldehyde, isovaleraldehyde, n-hexyl aldehyde, 2-ethylbutyl aldehyde, n-heptyl aldehyde, n-octyl aldehyde, 2-ethylhexyl aldehyde, n-nonyl aldehyde, n-decyl aldehyde, benzaldehyde, and cinnamaldehyde. Among them, aliphatic unbranched aldehydes having 2 to 6 carbon atoms are preferred, and n-butyl aldehyde is particularly preferred from the viewpoint of easily obtaining a polyvinyl acetal resin having a suitable breaking energy. These aldehydes can be used alone or in combination of two or more. Furthermore, polyfunctional aldehydes or aldehydes having other functional groups may be used in combination in an amount of 20% by mass or less of the total aldehydes. When n-butylaldehyde is used, the content of n-butylaldehyde in the aldehyde used for acetalization is preferably 50% by mass or more, more preferably 80% by mass or more, further preferably 95% by mass or more, particularly preferably 99% by mass or more, and may be 100% by mass.

[0116] The viscosity average degree of polymerization of the polyvinyl alcohol used as a raw material for the polyvinyl acetal resin is preferably 100 or more, more preferably 300 or more, more preferably 400 or more, even more preferably 600 or more, particularly preferably 700 or more, and most preferably 750 or more. When a polyvinyl acetal resin composition containing a large amount of plasticizer (for example, 20 parts by mass or more) is used, the viscosity average degree of polymerization of the polyvinyl alcohol used as a raw material for the polyvinyl acetal resin is preferably 500 or more, more preferably 900 or more, more preferably 1000 or more, even more preferably 1200 or more, particularly preferably 1500 or more, and most preferably 1600 or more. The viscosity average degree of polymerization of polyvinyl alcohol is preferably 5,000 or less, more preferably 3,000 or less, even more preferably 2,500 or less, particularly preferably 2,300 or less, and most preferably 2,000 or less. The viscosity average degree of polymerization of polyvinyl alcohol can be measured, for example, based on JIS K 6726 "Testing method for polyvinyl alcohol".

[0117] Usually, the viscosity average degree of polymerization of the polyvinyl acetal resin is equal to that of the raw material polyvinyl alcohol, and therefore the preferred viscosity average degree of polymerization of the polyvinyl alcohol is equal to that of the polyvinyl acetal resin. When the low dielectric layer contains two or more different polyvinyl acetal resins, it is preferable that the viscosity average degree of polymerization of at least one of the polyvinyl acetal resins is equal to or greater than the lower limit and equal to or less than the upper limit.

[0118] The amount of acetyl groups in the polyvinyl acetal resin constituting the low dielectric layer may be preferably 0.01 to 20% by mass, more preferably 0.05 to 10% by mass, and even more preferably 0.1 to 5% by mass, based on the ethylene units of the polyvinyl acetal main chain. The amount of acetyl groups in the polyvinyl acetal resin can be adjusted by appropriately adjusting the degree of saponification of the raw material polyvinyl alcohol or vinyl alcohol copolymer. When the low dielectric layer contains two or more different polyvinyl acetal resins, it is preferable that the amount of acetyl groups in at least one of the polyvinyl acetal resins is within the above range.

[0119] The degree of acetalization of the polyvinyl acetal resin used in the present invention is not particularly limited, but is preferably 40 to 86 mol%, more preferably 45 to 82 mol%, further preferably 50 to 78 mol%, particularly preferably 60 to 74 mol%, and most preferably 68 to 74 mol%. The degree of acetalization of the polyvinyl acetal resin can be adjusted within the above range by appropriately adjusting the amount of aldehyde used when acetalizing the polyvinyl alcohol resin. When the degree of acetalization is within the above range, the compatibility of the polyvinyl acetal resin with the plasticizer is unlikely to decrease. When the low dielectric layer contains two or more different polyvinyl acetal resins, it is preferable that the degree of acetalization of at least one of the polyvinyl acetal resins is within the above range.

[0120] The amount of hydroxyl groups in the polyvinyl acetal resin is preferably 6 to 26% by mass, more preferably 12 to 24% by mass, more preferably 15 to 22% by mass, and particularly preferably 18 to 21% by mass, based on the ethylene units in the polyvinyl acetal main chain. The amount of hydroxyl groups can be adjusted within the above range by adjusting the amount of aldehyde used when acetalizing the polyvinyl alcohol resin. When the low dielectric layer contains two or more different polyvinyl acetal resins, it is preferable that the amount of hydroxyl groups in at least one of the polyvinyl acetal resins is within the above range.

[0121] Polyvinyl acetal resins are usually composed of acetal group units, hydroxyl group units, and acetyl group units, and the amount of each of these units can be measured, for example, by JIS K 6728 "Testing Method for Polyvinyl Butyral" or nuclear magnetic resonance (NMR) spectroscopy. When a polyvinyl acetal resin contains units other than acetal group units, the amount of hydroxyl group units and the amount of acetyl group units are measured, and the amount of both units is subtracted from the amount of acetal group units in the case where no units other than acetal group units are contained, to calculate the amount of remaining acetal group units.

[0122] The low dielectric layer preferably contains uncrosslinked polyvinyl acetal from the viewpoint of obtaining good film-forming properties, but may contain crosslinked polyvinyl acetal. For example, the crosslinking method may be thermal self-crosslinking with carboxyl group-containing polyvinyl acetal, or intermolecular crosslinking with polyaldehyde, glyoxylic acid, or the like.

[0123] The viscosity of the polyvinyl acetal resin can be appropriately set depending on the type used. For example, when forming a thin low dielectric layer, the viscosity of a 10% by mass toluene / ethanol=1 / 1 (mass ratio) solution measured at 20°C and 30 rpm using a Brookfield (B-type) viscometer may be 100 to 1000 mPa·s, preferably 120 to 800 mPa·s, more preferably 150 to 600 mPa·s, even more preferably 180 to 500 mPa·s, and particularly preferably 200 to 400 mPa·s. By using a polyvinyl acetal resin having a viscosity in the above range, when bonding to a glass substrate by hot pressing, the heating temperature or heating time can be easily set to a desired range, and unmelted parts of the polyvinyl acetal resin can be made less likely to remain. In addition, even if the antenna system is exposed to high temperatures, the arrangement of the antenna circuit board can be prevented from shifting. The viscosity of the polyvinyl acetal resin can be adjusted by using or combining a polyvinyl acetal resin produced by using, as a raw material or as a part of a raw material, a polyvinyl alcohol-based resin having a high or low viscosity average polymerization degree. When the polyvinyl acetal resin used to form the low dielectric layer is a mixture of multiple resins, the viscosity is the viscosity of such a mixture.

[0124] Furthermore, the polyvinyl acetal resin may be combined with a known or commonly used plasticizer as necessary. Examples of the plasticizer include the following plasticizers. These plasticizers may be used alone or in combination of two or more. For example, a low dielectric layer may be formed as a plasticized polyvinyl acetal resin composition composed of a plasticizer and a polyvinyl acetal resin.

[0125] As the plasticizer, for example, the following can be used. · Esters of polyfunctional aliphatic or aromatic acids. Examples of the ester include dialkyl adipates (e.g., dihexyl adipate, di-2-ethylbutyl adipate, dioctyl adipate, di-2-ethylhexyl adipate, hexylcyclohexyl adipate, a mixture of heptyl adipate and nonyl adipate, diisononyl adipate, heptylnonyl adipate); esters of adipic acid and an alicyclic ester alcohol or an alcohol containing an ether compound (e.g., di(butoxyethyl) adipate, di(butoxyethoxyethyl) adipate); dialkyl sebacates (e.g., dibutyl sebacate); esters of sebacic acid and an alicyclic or an alcohol containing an ether compound; esters of phthalic acid (e.g., butyl benzyl phthalate, bis-2-butoxyethyl phthalate); and esters of alicyclic polyvalent carboxylic acids and aliphatic alcohols (e.g., 1,2-cyclohexanedicarboxylic acid diisononyl ester). Esters or ethers of polyhydric aliphatic or aromatic alcohols or oligoether glycols having one or more aliphatic or aromatic substituents. Examples include esters of glycerin, diglycol, triglycol, tetraglycol, etc. with linear or branched aliphatic or alicyclic carboxylic acids. Specific examples include diethylene glycol bis-(2-ethylhexanoate), triethylene glycol bis-(2-ethylhexanoate), triethylene glycol bis-(2-ethylbutanoate), tetraethylene glycol bis-n-heptanoate, triethylene glycol bis-n-heptanoate, triethylene glycol bis-n-hexanoate, tetraethylene glycol dimethyl ether, and dipropylene glycol benzoate. Phosphate esters of aliphatic or aromatic ester alcohols, such as tris(2-ethylhexyl) phosphate (TOF), triethyl phosphate, diphenyl-2-ethylhexyl phosphate, and tricresyl phosphate. Esters of citric acid, succinic acid and / or fumaric acid.

[0126] In addition, polyesters or oligoesters composed of polyhydric alcohols and polycarboxylic acids, terminal esterified or etherified products thereof, polyesters or oligoesters composed of lactones or hydroxycarboxylic acids, or terminal esterified or etherified products thereof, etc. may be used as plasticizers.

[0127] The content of the plasticizer may be, for example, 0 to 40 mass%, preferably 0 to 30 mass%, more preferably 0 to 15 mass%, even more preferably 0 to 10 mass%, and still more preferably 0 to 5 mass%, based on the total amount of the polyvinyl acetal resin and the plasticizer. A preferred polyvinyl acetal resin is commercially available, for example, from Kuraray Co., Ltd. under the name "Mobital (trademark)" and a preferred polyvinyl acetal resin film is commercially available, for example, from Kuraray Co., Ltd. under the name "Trosifol (trademark)".

[0128] Alternatively, when a low dielectric layer made of polyvinyl acetal resin is adhered to an adherend, a plasticizer may be further applied to a film made of polyvinyl acetal resin, and the adhesiveness of the polyvinyl acetal resin may be enhanced by the plasticizer. As such a plasticizer, the above-mentioned plasticizers may be used, and since the adhesiveness of the low dielectric layer can be improved, triethylene glycol-bis-(2-ethylbutanoate), triethylene glycol-bis-(2-ethylhexanoate), dihexyl adipate, dibutyl sebacate, di(butoxyethyl) adipate, and di(butoxyethoxyethyl) adipate are preferred, triethylene glycol-bis-(2-ethylhexanoate), di(butoxyethyl) adipate, and di(butoxyethoxyethyl) adipate are more preferred, and di(butoxyethyl) adipate and di(butoxyethoxyethyl) adipate are particularly preferred.

[0129] (Olefin-vinyl carboxylate copolymer resin) The olefin-vinyl carboxylate copolymer resin is not particularly limited as long as it has a lower dielectric constant than the first glass layer, and examples of the olefin include ethylene, propylene, n-butene, isobutylene, butadiene, and isoprene, and examples of the vinyl carboxylate include the vinyl ester compounds exemplified in the section on polyvinyl acetal resins. Among these, ethylene-vinyl acetate copolymer resins using ethylene as the olefin and vinyl acetate as the vinyl carboxylate compound are preferred because they can control the dielectric constant and have good adhesiveness.

[0130] The olefin-vinyl carboxylate copolymer resin may further be copolymerized with a monomer as a third component, as long as the dielectric constant can be controlled within a predetermined range. Examples of the monomer as the third component include acrylic acid esters, methacrylic acid esters, acrylamide and its derivatives, methacrylamide and its derivatives, vinyl ethers, nitriles, vinyl halides, vinylidene halides, allyl compounds, unsaturated carboxylic acids and their derivatives, and vinyl silyl compounds, as described in the section on polyvinyl acetal resins. These monomers can be used alone or in combination of two or more. When these other monomers are copolymerized, it is usually preferable to use these other monomers in a ratio of less than 10 mol% relative to the vinyl carboxylate compound.

[0131] In the olefin-vinyl carboxylate copolymer resin, from the viewpoint of strength, the ratio of vinyl carboxylate units to the total of olefin units and vinyl carboxylate units is, for example, preferably less than 50 mol%, more preferably 30 mol% or less, even more preferably 20 mol% or less, and particularly preferably 15 mol% or less. The lower limit of vinyl carboxylate is not particularly limited, but may be, for example, about 5 mol%. A preferred olefin-vinyl carboxylate copolymer resin is, for example, ethylene vinyl acetate, available from Tosoh Corporation under the trade name "Mersen (trademark)".

[0132] (Ionomer resin) The ionomer resin is not particularly limited, but may be a thermoplastic resin having a structural unit derived from an olefin such as ethylene and a structural unit derived from an α,β-unsaturated carboxylic acid, in which at least a part of the α,β-unsaturated carboxylic acid is neutralized with a metal ion, such as an alkali metal ion such as a sodium ion, an alkaline earth metal ion such as a magnesium ion, or a zinc ion.

[0133] In the ethylene-α,β-unsaturated carboxylic acid copolymer before being neutralized with metal ions, the content of the α,β-unsaturated carboxylic acid structural unit is preferably 2% by mass or more, more preferably 5% by mass or more, based on the mass of the ethylene-α,β-unsaturated carboxylic acid copolymer, and the content of the α,β-unsaturated carboxylic acid structural unit is preferably 30% by mass or less, more preferably 20% by mass or less.

[0134] Examples of structural units derived from α,β-unsaturated carboxylic acids contained in the ionomer resin include structural units derived from acrylic acid, methacrylic acid, maleic acid, monomethyl maleate, monoethyl maleate, and maleic anhydride, and among these, structural units derived from acrylic acid or methacrylic acid are particularly preferred.

[0135] As the ionomer resin, from the viewpoint of availability, an ionomer of an ethylene-acrylic acid copolymer and an ionomer of an ethylene-methacrylic acid copolymer are more preferable, and a zinc ionomer of an ethylene-acrylic acid copolymer, a sodium ionomer of an ethylene-acrylic acid copolymer, a zinc ionomer of an ethylene-methacrylic acid copolymer, and a sodium ionomer of an ethylene-methacrylic acid copolymer are particularly preferable. The ionomer resins can be used alone or in combination of two or more kinds. A preferred film made of ionomer resin is commercially available from Kuraray Co., Ltd. under the name "Sentryglass (trademark)".

[0136] (Acrylic resin) The acrylic resin is preferably a polymer obtained from an acrylic acid ester monomer and / or a methacrylic acid ester monomer, and examples of the monomer include alkyl acrylates such as methyl acrylate, ethyl acrylate, and n-propyl acrylate; modified acrylates such as glycidyl acrylate and 2-hydroxyethyl acrylate; ethylene glycol diacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, neopentyl glycol diacrylate, pentaerythritol, and the like. Rule Polyfunctional acrylates such as triacrylate; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, and n-propyl methacrylate; modified methacrylates such as glycidyl methacrylate and 2-hydroxyethyl methacrylate; ethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, polypropylene glycol dimethacrylate, neopentyl glycol dimethacrylate, pentaerythritol, Rule and polyfunctional methacrylates such as trimethacrylate. These monomers may be used alone or in combination of two or more.

[0137] In addition, copolymers of acrylic acid ester monomers and / or methacrylic acid ester monomers with unsaturated carboxylic acids such as acrylic acid and methacrylic acid; acrylamides such as N,N-dimethylacrylamide; aromatic vinyl compounds such as styrene and α-methylstyrene; and the like can also be suitably used as the acrylic resin.

[0138] A preferred acrylic resin is a liquid injection type resin marketed by Shinko Glass Industry Co., Ltd. under the name "3S Resin" or the like.

[0139] The low dielectric layer may contain known or conventional additives as necessary. Examples of the additives include solvents, plasticizers, ultraviolet absorbers, antioxidants, adhesion regulators, brighteners or fluorescent brighteners, stabilizers, dyes, processing aids, organic or inorganic nanoparticles, calcined silicic acid, and surfactants. The additives may be used alone or in combination.

[0140] (Antenna circuit board) The antenna circuit board includes at least one circuit layer and at least one high-frequency insulating layer, and its form is not particularly limited, and it can be used as various high-frequency circuit boards by known or conventional means.

[0141] The present invention also includes an antenna circuit board, and the antenna circuit board of the present invention can be usefully used in the antenna system of the present invention due to the high frequency characteristics derived from the high frequency insulating layer.

[0142] The circuit layer may be formed, for example, from at least a metal having electrical conductivity, and the circuit may be formed by using a known circuit processing method. The conductor forming the circuit layer may be any of various metals having electrical conductivity, such as gold, silver, copper, iron, nickel, aluminum, or alloy metals thereof.

[0143] In addition to the circuit layer, the antenna circuit board may also include a conductor layer such as a ground layer. The conductor layer may be made of various conductive metals, such as gold, silver, copper, iron, nickel, aluminum, or alloy metals thereof. The conductors constituting the circuit layer and the conductor layer may be the same or different.

[0144] The antenna circuit board may be used for various types of transmission lines, such as known or conventional transmission lines, such as coaxial lines, strip lines, microstrip lines, coplanar lines, and parallel lines, or may be used for antennas (for example, microwave or millimeter wave antennas).The circuit board may also be used for an antenna device in which an antenna and a transmission line are integrated.

[0145] The antenna structure may have any known or conventional structure as long as it uses a high-frequency insulating layer, and examples of such antennas include antennas that utilize millimeter waves or microwaves, such as a waveguide slot antenna, a horn antenna, a lens antenna, a chip antenna, a pattern antenna, a print antenna, a triplate antenna, a microstrip antenna, and a patch antenna. The antenna circuit board (or a semiconductor element mounting board) may be used in various sensors, particularly in vehicle-mounted radar.

[0146] The antenna circuit board may be a multi-layer circuit board having multiple circuit layers and / or conductor layers, or may be a circuit board (or a semiconductor device mounting board) on which a semiconductor device (e.g., an IC chip) is mounted.

[0147] The radio frequency antenna circuit board may be capable of supporting data transmission speeds of 10 gigabits per second or more. For example, the radio frequency antenna circuit board may be a circuit board compatible with 5G and next generation.

[0148] (High frequency insulation layer) The antenna circuit board includes a high-frequency insulating layer. The high-frequency insulating layer is not particularly limited as long as it is an insulating layer capable of reducing the transmission loss of an electric signal in a high-frequency circuit, and examples thereof include insulating layers made of heat-resistant resins such as thermoplastic liquid crystal polymer (LCP), polyimide (PI) (particularly modified polyimide (MPI)), polyethylene naphthalate (PEN), and polyether ether ketone (PEEK). Among these, an insulating layer made of polyimide is preferably used because it has excellent heat resistance and chemical resistance. In addition, a thermoplastic liquid crystal polymer is preferably used because of its excellent dielectric properties.

[0149] For example, the insulating layer may be formed from a thermoplastic liquid crystal polymer film or a polyimide film. In this case, a circuit layer or the like can be provided on the thermoplastic liquid crystal polymer film or the polyimide film to obtain an antenna circuit board.

[0150] In one direction in the plane of the high frequency insulating layer and perpendicular to it Exchange The dielectric constant εp in both directions may be, for example, 2.0 to 4.0, preferably 2.2 to 3.5, and more preferably 2.4 to 3.0, at a frequency of 28 GHz. Furthermore, the dielectric constant εf of the low dielectric layer and the dielectric constant εp of the high frequency insulating layer may be εf / εp=30 / 70 to 60 / 40, preferably 35 / 65 to 60 / 40, and more preferably 38 / 62 to 55 / 45.

[0151] In one direction in the plane of the high frequency insulating layer and perpendicular to it Exchange The dielectric loss tangent tan δp in both directions may be, for example, 0.010 or less, preferably 0.005 or less, and more preferably 0.003 or less at a frequency of 28 GHz. Here, the dielectric properties are values ​​measured by the above-mentioned method.

[0152] From the viewpoint of excellent heat resistance, an insulating layer made of polyimide (hereinafter, sometimes referred to as a polyimide insulating layer) is preferable. The polyimide is not particularly limited as long as it is a polymer having an imide group in a structural unit, and examples thereof include polyimide-based resins such as polyimide, polyamideimide, polybenzimidazole, polyimide ester, polyetherimide, and polysiloxaneimide.

[0153] Polyimide can be formed by imidizing (curing) a precursor polyamic acid. Polyamic acid can be synthesized by reacting a known diamine with a tetracarboxylic acid (including its acid anhydride) in the presence of a solvent. As the diamine, an aromatic diamine, an aliphatic diamine, an alicyclic diamine, etc. can be used, and from the viewpoint of heat resistance, an aromatic diamine is preferable. As the aromatic diamine, for example, 4,4'-diaminodiphenyl ether, 2'-methoxy-4,4'-diaminobenzanilide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 4,4'-diaminobenzanilide, 5-amino-2-(p-aminophenyl)benzoxazole, etc. can be mentioned. As the tetracarboxylic acid, an aromatic tetracarboxylic acid, an aliphatic tetracarboxylic acid, an alicyclic tetracarboxylic acid, an anhydride thereof, etc. can be used, and from the viewpoint of heat resistance, an aromatic tetracarboxylic acid anhydride is preferable. As the aromatic tetracarboxylic acid anhydride, for example, pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride, 4,4'-oxydiphthalic anhydride, etc. can be mentioned. Each of these diamines and tetracarboxylic acids can be used alone or in combination of two or more kinds.

[0154] The polyimide film used in the polyimide insulating layer can be produced, for example, by applying a solution of polyamic acid (polyimide precursor) obtained by reacting diamine with tetracarboxylic acid to a support, drying the solution to obtain a polyamic acid film, and then heat-treating the film to harden (imidize). The polyamic acid solution can be applied by known application methods such as spin coating, comma coater, screen printing, slit coating, roll coating, knife coating, dip coating, and die coating.

[0155] Various additives, fillers, etc. may be added to the polyimide film within the range that does not impair the effects of the present invention.

[0156] Polyimide films are commercially available, for example, under the trade names Kapton EN, Kapton H, and Kapton V manufactured by DuPont-Toray Co., Ltd., Apical NPI (trade name) manufactured by Kaneka Corporation, and Upilex S (trade name) manufactured by Ube Industries, Ltd.

[0157] From the viewpoint of excellent dielectric properties, an insulating layer made of a thermoplastic liquid crystal polymer (hereinafter, sometimes referred to as a thermoplastic liquid crystal polymer insulating layer) is preferable. The thermoplastic liquid crystal polymer film used in the thermoplastic liquid crystal polymer insulating layer is formed from a liquid crystal polymer that can be melt-formed. This thermoplastic liquid crystal polymer is a polymer that can form an optically anisotropic molten phase, and as long as it is a liquid crystal polymer that can be melt-formed, its chemical composition is not particularly limited, but examples thereof include thermoplastic liquid crystal polyester, or thermoplastic liquid crystal polyester amide in which an amide bond is introduced therein.

[0158] The thermoplastic liquid crystal polymer may be a polymer in which an imide bond, a carbonate bond, a carbodiimide bond, or a bond derived from an isocyanate such as an isocyanurate bond is further introduced into an aromatic polyester or an aromatic polyester amide.

[0159] Specific examples of the thermoplastic liquid crystal polymer used in the present invention include known thermoplastic liquid crystal polyesters and thermoplastic liquid crystal polyesteramides derived from the compounds classified into (1) to (4) below and their derivatives. However, it goes without saying that there is an appropriate range for the combination of various raw material compounds in order to form a polymer capable of forming an optically anisotropic molten phase.

[0160] (1) Aromatic or aliphatic dihydroxy compounds (see Table 1 for representative examples) [Table 1]

[0161] (2) Aromatic or aliphatic dicarboxylic acids (see Table 2 for representative examples) [Table 2]

[0162] (3) Aromatic hydroxycarboxylic acids (see Table 3 for representative examples) [Table 3]

[0163] (4) Aromatic diamines, aromatic hydroxyamines, or aromatic aminocarboxylic acids (see Table 4 for representative examples) [Table 4]

[0164] Representative examples of thermoplastic liquid crystal polymers obtained from these raw material compounds include copolymers having the structural units shown in Tables 5 and 6.

[0165] [Table 5]

[0166] [Table 6]

[0167] Among these copolymers, polymers containing at least p-hydroxybenzoic acid and / or 6-hydroxy-2-naphthoic acid as repeating units are preferred, and in particular, (i) polymers containing repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, or (ii) copolymers containing repeating units of at least one aromatic hydroxycarboxylic acid selected from the group consisting of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, at least one aromatic diol and / or aromatic hydroxyamine, and at least one aromatic dicarboxylic acid are preferred.

[0168] For example, in the case of polymer (i), when the thermoplastic liquid crystal polymer contains at least repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, the molar ratio (A) / (B) of the p-hydroxybenzoic acid in the repeating unit (A) to the 6-hydroxy-2-naphthoic acid in the repeating unit (B) in the thermoplastic liquid crystal polymer is preferably about (A) / (B)=10 / 90 to 90 / 10, more preferably about (A) / (B)=15 / 85 to 85 / 15, and even more preferably about (A) / (B)=20 / 80 to 80 / 20.

[0169] In the case of the polymer (ii), at least one aromatic hydroxycarboxylic acid (C) selected from the group consisting of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, at least one aromatic diol (D) selected from the group consisting of 4,4'-dihydroxybiphenyl, hydroquinone, phenylhydroquinone, and 4,4'-dihydroxydiphenyl ether, and at least one aromatic dicarbohydrate (E) selected from the group consisting of terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid are mixed. The molar ratio of each repeating unit of the aromatic hydroxycarboxylic acid (C): the aromatic diol (D): the aromatic dicarboxylic acid (E) in the thermoplastic liquid crystal polymer may be about (30-80): (35-10): (35-10), more preferably about (C): (D): (E) = (35-75): (32.5-12.5): (32.5-12.5), and even more preferably about (C): (D): (E) = (40-70): (30-15): (30-15).

[0170] The molar ratio of repeating units derived from 6-hydroxy-2-naphthoic acid in the aromatic hydroxycarboxylic acid (C) may be, for example, 85 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more. The molar ratio of repeating units derived from 2,6-naphthalenedicarboxylic acid in the aromatic dicarboxylic acid (E) may be, for example, 85 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more.

[0171] The aromatic diol (D) may be repeating units (D1) and (D2) derived from two different aromatic diols selected from the group consisting of hydroquinone, 4,4'-dihydroxybiphenyl, phenylhydroquinone, and 4,4'-dihydroxydiphenyl ether. In this case, the molar ratio of the two aromatic diols (D1) / (D2) may be 23 / 77 to 77 / 23, more preferably 25 / 75 to 75 / 25, and even more preferably 30 / 70 to 70 / 30.

[0172] The molar ratio of the repeating structural units derived from the aromatic diol to the repeating structural units derived from the aromatic dicarboxylic acid is preferably (D) / (E)=95 / 100 to 100 / 95. If it is outside this range, the degree of polymerization does not increase and the mechanical strength tends to decrease.

[0173] The ability to form an optically anisotropic molten phase in the present invention can be confirmed, for example, by placing a sample on a hot stage, heating it in a nitrogen atmosphere, and observing the light transmitted through the sample.

[0174] The preferred thermoplastic liquid crystal polymer may have a melting point (hereinafter referred to as Tm0) in the range of 200 to 360°C, preferably in the range of 240 to 360°C, more preferably in the range of 260 to 360°C, and even more preferably in the range of 270 to 350°C. Tm0 is determined by measuring the temperature at which the main endothermic peak appears using a differential scanning calorimeter (Shimadzu Corporation DSC). That is, the thermoplastic liquid crystal polymer sample is heated at a rate of 10°C / min to completely melt it, and then the melt is cooled to 50°C at a rate of 10°C / min, and the position of the endothermic peak that appears after heating again at a rate of 10°C / min is determined as the melting point of the thermoplastic liquid crystal polymer sample.

[0175] Thermoplastic polymers such as polyethylene terephthalate, modified polyethylene terephthalate, polyolefin, polycarbonate, polyarylate, polyamide, polyphenylene sulfide, polyether ether ketone, and fluororesin, various additives, fillers, and the like may be added to the thermoplastic liquid crystal polymer within a range that does not impair the effects of the present invention.

[0176] The thermoplastic liquid crystal polymer film is obtained, for example, by extrusion molding the melt kneaded product of the thermoplastic liquid crystal polymer. Any method can be used as the extrusion molding method, but the well-known T-die method, inflation method, etc. are industrially advantageous. In particular, in the inflation method, stress is applied not only in the mechanical axis direction (hereinafter abbreviated as MD) of the thermoplastic liquid crystal polymer film, but also in the direction perpendicular thereto (hereinafter abbreviated as TD), and the film can be uniformly stretched in the MD and TD directions, so that a thermoplastic liquid crystal polymer film with controlled molecular orientation, dielectric properties, etc. in the MD and TD directions can be obtained.

[0177] If necessary, a known or conventional heat treatment may be performed to adjust the melting point and / or thermal expansion coefficient of the thermoplastic liquid crystal polymer film. The heat treatment conditions can be appropriately set according to the purpose, and for example, the melting point (Tm) of the thermoplastic liquid crystal polymer film may be increased by heating for several hours at a temperature equal to or higher than the melting point (Tm0)-10°C (for example, about Tm0-10°C to Tm0+30°C, preferably about Tm0°C to Tm0+20°C).

[0178] By providing a circuit layer and / or a conductor layer on the obtained thermoplastic liquid crystal polymer film by a known or conventional method, it is possible to prepare an antenna circuit board having a thermoplastic liquid crystal polymer insulating layer.

[0179] The melting point (Tm) of the thermoplastic liquid crystal polymer insulating layer may be, for example, 200 to 380°C, and preferably in the range of 240 to 370°C. The melting point (Tm) of the thermoplastic liquid crystal polymer insulating layer can be obtained by observing the thermal behavior of a sample obtained from the thermoplastic liquid crystal polymer insulating layer (or thermoplastic liquid crystal polymer film) using a differential scanning calorimeter. That is, the position of the endothermic peak that appears when the temperature of the thermoplastic liquid crystal polymer film sample is raised at a rate of 10°C / min can be determined as the melting point (Tm) of the thermoplastic liquid crystal polymer film.

[0180] The thermoplastic liquid crystal polymer insulating layer may have, for example, a thermal expansion coefficient of 0 to 25 ppm / ° C., and the thermal expansion coefficient may preferably be about 5 to 22 ppm / ° C. The thermal expansion coefficient can be understood as a value measured using a thermomechanical analyzer (TMA) between 30° C. and 150° C. when the temperature is raised from 25° C. to 200° C. at a rate of 5° C. / min, cooled to 30° C. at a rate of 20° C. / min, and then raised again at a rate of 5° C. / min. EXAMPLES

[0181] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0182] [Dielectric constant and dissipation factor] The dielectric constant and dielectric loss tangent of the films used in the following low dielectric layers and high frequency insulating layers were measured in accordance with JIS R 1660-2 at a frequency of 28GHz (25℃) using a Fabry-Perot resonator (Model No. DPS03, manufactured by Keycom Corporation). The measurements were performed in one direction on a plane and in the direction perpendicular to the plane. Exchange The experiment was carried out in both directions (X and Y directions).

[0183] [Antenna circuit board, low dielectric layer thickness] The thickness of the antenna circuit board was measured using a micrometer (Model 227-201-CLM-15QM, manufactured by Mitutoyo Corporation) on the antenna circuit board. The thickness of the low dielectric layer was measured using a film used as the low dielectric layer. The thickness of the low dielectric layer may be obtained by measuring the thickness of the entire antenna system, and the thickness of the antenna circuit board and glass in the antenna system, and subtracting the thickness of the antenna circuit board and glass from the thickness of the entire antenna system.

[0184] [Polyvinyl acetal resin solution viscosity] The polyvinyl acetal resin constituting the polyvinyl acetal resin film was dissolved in a mixed solvent of toluene / ethanol = 1 / 1 (mass ratio) to a concentration of 10 mass % to prepare a solution. The viscosity of this solution was measured using a Brookfield type (B type) viscometer at 20 ° C. and a rotation speed of 30 rpm.

[0185] [Example 1] <Fabrication of antenna circuit board> Copper foil (Fukuda Metal Foil and Powder Co., Ltd., electrolytic copper foil "H9A", thickness 12 μm) was superimposed on both sides of a thermoplastic liquid crystal polymer film (Kuraray Co., Ltd., Vecstar (registered trademark), thickness 50 μm, dielectric constant in X direction: 3.4, dielectric constant in Y direction: 3.4, dielectric loss tangent in X direction: 0.002, dielectric loss tangent in Y direction: 0.002) and a vacuum hot press was used to set the heating plate to 290 ° C. and press the film under a pressure of 4 MPa for 15 minutes to produce a copper-clad laminate having a copper foil / thermoplastic liquid crystal polymer film / copper foil configuration. A part of the copper foil on one side of the obtained copper-clad laminate was removed with an etching solution to form a circuit, and this operation was repeated to produce an antenna circuit board (length 5 cm, width 5 cm) having a thickness of 400 μm.

[0186] <Preparation of polyvinyl acetal resin film> Polyvinyl butyral resin 1 (hydroxyl group amount 19.8 mass%, acetalization degree 70.8 mol%, acetyl group amount 1.0 mass%, resin viscosity 152 mPa s) and polyvinyl butyral resin 2 (hydroxyl group amount 20.1 mass%, acetalization degree 70.4 mol%, acetyl group amount 0.9 mass%, resin viscosity 1410 mPa s) were blended in a mass ratio of 75:25, melt-kneaded, extruded into strands, and pelletized. The resulting pellets were melt-extruded using a single-screw extruder and a T-die, and a polyvinyl acetal resin film with a smooth surface and a thickness of 50 μm (dielectric constant in X direction: 2.5, dielectric constant in Y direction: 2.5, dielectric loss tangent in X direction: 0.01, dielectric loss tangent in Y direction: 0.01, plasticizer content: 0 mass%, resin viscosity: 245 mPa s) was obtained.

[0187] <Preparation of Laminate> On a lower glass of 20 cm in length, 10 cm in width, and 3 mm in thickness, a Teflon (registered trademark) sheet with one side embossing, the dried polyvinyl acetal resin film prepared above, 5 cm in length, 5 cm in width, and 50 μm in thickness, the antenna circuit board prepared above (5 cm in length, 5 cm in width), a Teflon (registered trademark) sheet with one side embossing, and an upper glass of 5 cm in length, 5 cm in width, and 3 mm in thickness were stacked and fixed in this order. Note that the polyvinyl acetal resin film, the antenna circuit board, and the upper glass were aligned so that they overlapped with each other. The Teflon (registered trademark) sheet adjacent to the polyvinyl acetal resin film was placed so that the embossed surface was in contact with the polyvinyl acetal resin film. The Teflon (registered trademark) sheet adjacent to the antenna circuit board was placed so that the mirror surface was in contact with the antenna circuit board. The antenna circuit board was placed so that the surface having the circuit was in contact with the polyvinyl acetal resin film. These were heated in a vacuum laminator at 140°C for 15 minutes under vacuum, and then the upper chamber was set to -10 kPa (differential pressure with the lower chamber: approximately 90 kPa) and held for 15 minutes. The pressure was then returned to normal pressure, and the Teflon (registered trademark) sheets and upper and lower glass placed above and below were removed to produce a laminate in the following order: polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer).

[0188] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) was placed on a lower glass with a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (low dielectric layer) was in contact with the lower glass, and a Teflon (registered trademark) sheet and an upper glass with a length of 5 cm, a width of 5 cm, and a thickness of 3 mm were placed on top of it and fixed in this order. The antenna circuit board was disposed in an area 2 cm to 7 cm inward from the vertical end of the lower glass. The laminate and the upper glass were aligned so that they overlapped each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber was about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the Teflon (registered trademark) sheet and the upper glass were removed, and an antenna system was obtained in which glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna circuit board was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breaks or deformations of the circuit were observed. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0189] [Example 2] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) obtained in Example 1 was placed on the lower glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (low dielectric layer) was in contact with the lower glass, and the dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1 and a thin glass having a length of 5 cm, a width of 5 cm, and a thickness of 1 mm were placed on top of it and fixed in this order. The antenna circuit board was disposed in an area 2 cm to 7 cm inward from the vertical end of the lower glass. The laminate and the thin glass were aligned so that they overlap each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber was about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was arranged on a part of the glass to obtain an antenna system. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0190] [Example 3] <Preparation of Laminate> On a glass plate measuring 20 cm in length, 10 cm in width and 3 mm in thickness, a Teflon (registered trademark) sheet with one side embossing, a dried polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 50 μm in thickness prepared in Example 1, an antenna circuit board (5 cm in length, 5 cm in width) prepared in Example 1, a dried polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 50 μm in thickness prepared in Example 1, and a thin glass plate measuring 5 cm in length, 5 cm in width and 1 mm in thickness were stacked and fixed in this order. The polyvinyl acetal resin film, the antenna circuit board and the thin glass plate were aligned so as to overlap each other. The Teflon sheet was placed so that the embossed surface was in contact with the polyvinyl acetal resin film, and the antenna circuit board was placed so that the surface having the circuit was in contact with the polyvinyl acetal resin film adjacent to the Teflon sheet. These were heated in a vacuum laminator at 140°C for 15 minutes under vacuum, and then the upper chamber was set to -10 kPa (differential pressure with the lower chamber: approximately 90 kPa) and held for 15 minutes. The pressure was then returned to normal pressure and the Teflon (registered trademark) sheet and glass were removed to produce a laminate in the following order: polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer).

[0191] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) was fixed on a piece of glass measuring 20 cm long, 10 cm wide, 3 mm thick, with a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (low dielectric layer) was in contact with the glass. The laminate was placed on the glass in an area 2 cm to 7 cm inward from the end of the glass in the vertical direction. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber was about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was arranged on a part of the glass to obtain an antenna system. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0192] [Example 4] <Preparation of Laminate> On the lower glass having a length of 20 cm, a width of 10 cm, and a thickness of 3 mm, a Teflon (registered trademark) sheet with one side embossing, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, an antenna circuit board (length of 5 cm, width of 5 cm) prepared in Example 1, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, a Teflon (registered trademark) sheet with one side embossing, and an upper glass having a length of 5 cm, a width of 5 cm, and a thickness of 3 mm were stacked and fixed in this order. The Teflon (registered trademark) sheet was arranged so that the embossed surface was in contact with the polyvinyl acetal resin film. The antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film on the lower glass side. These were heated in a vacuum laminator at 140°C for 15 minutes under vacuum, and then the upper chamber was set to -10 kPa (differential pressure with the lower chamber: approximately 90 kPa) and held for 15 minutes. The pressure was then returned to normal pressure, and the Teflon (registered trademark) sheets and upper and lower glass placed above and below were removed to produce a laminate in the following order: polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer).

[0193] <Fabrication of antenna system> The laminate (5 cm long, 5 cm wide) was placed on a glass with a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (low dielectric layer) adjacent to the circuit layer was in contact with the glass, and a thin glass sheet with a length of 5 cm, a width of 5 cm, and a thickness of 1 mm was placed on top of it and fixed. The antenna circuit board was disposed in an area 2 cm to 7 cm inward from the longitudinal end of the glass. The laminate and the thin glass sheet were aligned so that they overlapped each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber was about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was arranged on a part of the glass to obtain an antenna system. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0194] [Example 5] <Preparation of Laminate> Instead of the polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm, a plasticized polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 0.38 mm (dielectric constant in the X direction: 2.7, dielectric constant in the Y direction: 2.7, dielectric loss tangent in the X direction: 0.02, dielectric loss tangent in the Y direction: 0.02) containing 72 mass% of polyvinyl butyral resin (hydroxyl group amount 28.8 mass%, viscosity average polymerization degree 1700) and 28 mass% of triethylene glycol-bis-(2-ethylhexanoate) was used. A laminate was produced in the same manner as in Example 1, in which the plasticized polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order.

[0195] <Fabrication of antenna system> Except for using the above laminate instead of the laminate of Example 1, the laminate was laminated in the order of glass (first glass layer), plasticized polyvinyl acetal resin film (low dielectric layer), circuit (circuit layer), antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), and copper foil (conductor layer) in the same manner as in Example 1, and an antenna circuit board was disposed on a part of the glass to obtain an antenna system. No partial peeling or foaming was observed in the obtained antenna system, and no breaks or deformations of the circuit were observed. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0196] [Example 6] <Fabrication of antenna system> The laminate of Example 5 was used instead of the laminate of Example 1, and the plasticized polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 0.38 mm in thickness used in Example 5 was used instead of the polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness used in Example 5. Except for this, the laminate was laminated in the order of glass (first glass layer) / plasticized polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / plasticized polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) in order, and an antenna circuit board with a protective glass plate was disposed on a part of the glass to obtain an antenna system. No partial peeling or foaming was observed in the obtained antenna system, and no disconnection or deformation of the circuit was observed. Furthermore, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0197] [Example 7] <Preparation of Laminate> A laminate was produced in the same manner as in Example 1, except that a 5 cm long, 5 cm wide, 50 μm thick ionomer resin film (Kuraray Co., Ltd., SentryGlas (registered trademark) SG5000 thinned by heat pressing, X-direction dielectric constant: 2.2, Y-direction dielectric constant: 2.2, X-direction dielectric loss tangent: 0.002, Y-direction dielectric loss tangent: 0.002) was used instead of the 5 cm long, 5 cm wide, 50 μm thick polyvinyl acetal resin film. The laminate was produced in the same manner as in Example 1, except that a 5 cm long, 5 cm wide, 50 μm thick ionomer resin film ... (Kuraray Co., Ltd., SentryGlas (registered trademark) SG5000 thinned by heat pressing, X-direction dielectric constant: 2.2, Y-direction dielectric loss tangent: 0.002, Y-direction dielectric loss tangent: 0.002) was used instead of the 5 cm long, 5 cm wide, 50 μm thick polyvinyl acetal resin film. The laminate was produced in the same manner as in Example 1, except that a 5 cm long, 5 cm wide, 50 μm thick ionomer resin film was used instead of the 5 cm long, 5 cm wide, 50 μm thick polyvinyl acetal resin film (Kuraray Co., Ltd., SentryGlas (registered trademark) SG5000 thinned by heat pressing, X-direction dielectric constant: 2.2, Y-

[0198] <Fabrication of antenna system> The laminate of Example 1 was replaced with the above laminate, and the polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness was replaced with an ionomer resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness (a film made by thinning SentryGlas (registered trademark) SG5000 by heat pressing, manufactured by Kuraray Co., Ltd.) was replaced with an ionomer resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness. The laminate was laminated in the order of glass (first glass layer), ionomer resin film (low dielectric layer), circuit (circuit layer), antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), ionomer resin film (low dielectric layer), and thin glass (protective layer), and an antenna circuit board with a protective glass plate was disposed on a part of the glass to obtain an antenna system. No partial peeling or foaming was observed in the obtained antenna system, and no disconnection or deformation of the circuit was observed. Furthermore, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0199] [Example 8] <Preparation of Laminate> A laminate is prepared in the same manner as in Example 1, except that a polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 30 μm in thickness is used instead of the polyvinyl acetal resin film measuring 5 cm in length, 5 cm in width and 50 μm in thickness, and a laminate is prepared in the following order: polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer).

[0200] <Fabrication of antenna system> Except for using the above laminate instead of the laminate of Example 1, the laminate is laminated in the same manner as in Example 2 in the order of glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer), and an antenna circuit board with a protective glass plate is arranged on a part of the glass to obtain an antenna system. The polyvinyl acetal resin film with a thickness of 30 μm is composed of the same polyvinyl acetal resin as the polyvinyl acetal resin film produced in Example 1, so it is presumed to have the same dielectric constant. In the obtained antenna system, the low dielectric layer has a dielectric constant smaller than that of the glass, so it is presumed that the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0201] [Example 9] <Fabrication of antenna system> On the lower glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, the dried polyvinyl acetal resin film produced in Example 1 having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm, the antenna circuit board (length of 5 cm, width of 5 cm) produced in Example 1, a Teflon (registered trademark) sheet, and an upper glass having a length of 5 cm, a width of 5 cm, and a thickness of 3 mm were stacked and fixed in this order. The antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film. The polyvinyl acetal resin film, the antenna circuit board, and the upper glass were aligned so that they overlapped with each other. These were heated at 140°C for 15 minutes under vacuum in a vacuum laminator, and then the upper chamber was set to -10kPa (pressure difference with the lower chamber was about 90kPa) and held for 15 minutes, and then the pressure was returned to normal pressure, and the Teflon (registered trademark) sheet and the upper glass were removed, and an antenna system was obtained in which glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna circuit board was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breaks or deformations of the circuit were observed. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0202] [Example 10] <Fabrication of antenna system> On the lower glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, an antenna circuit board (length of 5 cm, width of 5 cm) prepared in Example 1, a dried polyvinyl acetal resin film having a length of 5 cm, a width of 5 cm, and a thickness of 50 μm prepared in Example 1, and a thin glass plate having a length of 5 cm, a width of 5 cm, and a thickness of 1 mm were stacked and fixed in this order. The antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film on the lower glass side. The antenna circuit board was arranged in an area 2 cm to 7 cm inward from the vertical end of the lower glass. The antenna circuit board, the two polyvinyl acetal resin films, and the thin glass sheet were aligned so as to overlap each other. These were placed in a vacuum bag, and after decompressing at room temperature for 15 minutes, the temperature was raised to 135°C while still under reduced pressure and held for 30 minutes, and then the temperature was lowered and the reduced pressure was released to obtain an antenna system in which the glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breaks or deformations were observed in the circuit. In addition, in the obtained antenna system, since the low dielectric layer has a smaller dielectric constant than the glass, high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0203] [Example 11] <Fabrication of antenna system> The same procedure as in Example 9 was used except that a plasticized polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 0.38 mm in thickness was used instead of the polyvinyl acetal resin film of 5 cm in length, 5 cm in width, and 50 μm in thickness used in Example 5. The glass (first glass layer) / plasticized polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) were laminated in this order, and an antenna circuit board was disposed on a part of the glass to obtain an antenna system. No partial peeling or foaming was observed in the obtained antenna system, and no breaks or deformations were observed in the circuit. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0204] [Example 12] <Fabrication of antenna system> On a glass having a length of 20 cm, a width of 10 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, a dried plasticized polyvinyl acetal resin film having a length of 7 cm, a width of 7 cm, and a thickness of 0.38 mm used in Example 5, an antenna circuit board (length of 5 cm, width of 5 cm) prepared in Example 1 in the center of the plasticized polyvinyl acetal resin film, a dried polyvinyl acetal resin film having a length of 7 cm, a width of 7 cm, and a thickness of 50 μm prepared in Example 1, and a thin glass plate having a length of 7 cm, a width of 7 cm, and a thickness of 1 mm were stacked and fixed in this order. The antenna circuit board was arranged so that the surface having the circuit was in contact with the plasticized polyvinyl acetal resin film. The antenna circuit board was arranged in an area 2 cm to 7 cm inward from the longitudinal end of the glass. The two polyvinyl acetal resin films and the thin glass sheet were aligned so as to overlap each other. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still decompressed, and held for 30 minutes. After that, the temperature was lowered, the decompression was released, and the material was temporarily pressed. The material was then placed in an autoclave and treated at 140°C and 12MPa for 30 minutes to obtain an antenna system in which the glass (first glass layer) / plasticized polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was disposed on a part of the glass. No partial peeling or foaming was observed in the obtained antenna system, and no breakage or deformation of the circuit was observed. In addition, in the obtained antenna system, since the low dielectric layer has a smaller dielectric constant than the glass, high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0205] [Example 13] <Fabrication of antenna system> The laminate obtained in Example 1 was laminated on a lower glass having a length of 30 cm, a width of 30 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01, so that the polyvinyl acetal resin film (low dielectric layer) was in contact with the lower glass, and on top of that, a plasticized polyvinyl acetal resin intermediate film having a length of 30 cm, a width of 30 cm, and a thickness of 0.76 mm, containing 72% by mass of polyvinyl butyral resin (hydroxyl group amount 28.8% by mass, viscosity average polymerization degree 1700) and 28% by mass of triethylene glycol-bis-(2-ethylhexanoate), and an upper glass having a length of 30 cm, a width of 30 cm, and a thickness of 3 mm were laminated and fixed in this order. The antenna circuit board was disposed in the center of the surface direction of the lower glass. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still under reduced pressure, and held for 30 minutes. After that, the temperature was lowered, the decompression was released, and the material was temporarily pressed. The material was then placed in an autoclave and treated at 140°C and 12MPa for 30 minutes to obtain an antenna system in which the layers were laminated in the order of glass (first glass layer), polyvinyl acetal resin film (first low dielectric layer), circuit (circuit layer), antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), plasticized polyvinyl acetal resin intermediate film (second low dielectric layer), and glass (second glass layer), and the antenna circuit board was sealed inside the laminated glass. In the antenna system obtained, no foaming or significant optical unevenness was observed around the antenna circuit. In addition, in the antenna system obtained, the low dielectric layer has a smaller dielectric constant than the glass, so that high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0206] [Example 14] <Fabrication of antenna system> A dried polyvinyl acetal resin film of 7 cm in length, 7 cm in width, and 50 μm in thickness produced in Example 1 was superimposed on a lower glass having a length of 30 cm, a width of 30 cm, a thickness of 3 mm, a dielectric constant in the X direction: 6.5, a dielectric constant in the Y direction: 6.5, a dielectric loss tangent in the X direction: 0.01, and a dielectric loss tangent in the Y direction: 0.01. The antenna circuit board (5 cm in length, 5 cm in width) produced in Example 1 was superimposed and arranged in the center of the polyvinyl acetal resin film, and a plasticized polyvinyl acetal resin intermediate film of 30 cm in length, 30 cm in width, and 0.76 mm in thickness used in Example 13 and an upper glass having a length of 30 cm in length, 30 cm in width, and a thickness of 3 mm were superimposed and fixed in this order. The antenna circuit board was arranged so that the surface having the circuit was in contact with the polyvinyl acetal resin film. The antenna circuit board was disposed in the center of the surface direction of the lower glass. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still under reduced pressure, and held for 30 minutes. After that, the temperature was lowered, the decompression was released, and the material was temporarily pressed. The material was then placed in an autoclave and treated at 140°C and 12MPa for 30 minutes to obtain an antenna system in which the layers were laminated in the order of glass (first glass layer), polyvinyl acetal resin film (first low dielectric layer), circuit (circuit layer), antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), plasticized polyvinyl acetal resin intermediate film (second low dielectric layer), and glass (second glass layer), and the antenna circuit board was sealed inside the laminated glass. In the antenna system obtained, no foaming or significant optical unevenness was observed around the antenna circuit. In addition, in the antenna system obtained, the low dielectric layer has a smaller dielectric constant than the glass, so that high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0207] [Example 15] <Fabrication of antenna system> An ionomer resin film (manufactured by Kuraray Co., Ltd., SentryGlas (registered trademark) SG5000 thinned by heat pressing, X-direction dielectric constant: 2.2, Y-direction dielectric constant: 2.2, X-direction dielectric tangent: 0.002, Y-direction dielectric tangent: 0.002) measuring 7 cm in length, 7 cm in width, and 50 μm in thickness was placed on the lower glass having dimensions of 30 cm in length, 30 cm in width, 3 mm in thickness, dielectric constant in the X direction: 6.5, dielectric constant in the Y direction: 6.5, dielectric tangent in the X direction: 0.01, and dielectric tangent in the Y direction: 0.01) and the antenna circuit board (5 cm in length, 5 cm in width) produced in Example 1 was placed on the center of the polyvinyl acetal resin film, and a dried ionomer resin intermediate film (manufactured by Kuraray Co., Ltd., SentryGlas (registered trademark) The lower glass was fixed in place with a thickness of 30 mm and a thickness of 30 cm. The antenna circuit board was placed so that the surface with the circuit was in contact with the ionomer resin film. The antenna circuit board was placed in the center of the surface of the lower glass. These were placed in a vacuum bag, decompressed at room temperature for 15 minutes, heated to 100°C while still under reduced pressure, and held for 30 minutes. After that, the temperature was lowered, the decompression was released, and the material was temporarily pressed. The material was then placed in an autoclave and treated at 135°C and 12MPa for 30 minutes to obtain an antenna system in which the layers were laminated in the order of glass (first glass layer), ionomer resin film (first low dielectric layer), circuit (circuit layer), antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), copper foil (conductor layer), ionomer resin intermediate film (second low dielectric layer), and glass (second glass layer), and the antenna circuit board was sealed inside the laminated glass. In the antenna system obtained, no bubbles or large optical irregularities were observed around the antenna circuit. In addition, in the antenna system obtained, the low dielectric layer has a smaller dielectric constant than the glass, so that the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0208] [Example 16] <Fabrication of antenna system> An appropriate amount of triethylene glycol-di-(2-ethylhexanoate) was applied to the polyvinyl acetal resin film surface of the laminate obtained in Example 1, and the laminate was attached to a glass sheet having dimensions of 20 cm length, 10 cm width, 3 mm thickness, X-direction dielectric constant: 6.5, Y-direction dielectric constant: 6.5, X-direction dielectric loss tangent: 0.01, and Y-direction dielectric loss tangent: 0.01, without allowing air to enter the glass sheet. The antenna circuit board was disposed in an area 2 cm to 7 cm inward from the longitudinal end of the glass sheet. These were heated for 1 hour in a hot air dryer at 50°C to obtain an antenna system in which the layers were laminated in the order of glass (first glass layer), polyvinyl acetal resin film (low dielectric layer), circuit (circuit layer), antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer), and copper foil (conductor layer), with the antenna circuit board disposed on a portion of the glass. No film shift was observed even when shear force was applied to the obtained antenna system. In addition, in the obtained antenna system, the low dielectric layer has a smaller dielectric constant than the glass, so that high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0209] [Example 17] <Fabrication of antenna system> An appropriate amount of triethylene glycol-di-(2-ethylhexanoate) was applied to the polyvinyl acetal resin film surface of the laminate obtained in Example 3, and the laminate was attached to a glass sheet having dimensions of 20 cm length, 10 cm width, 3 mm thickness, X-direction dielectric constant: 6.5, Y-direction dielectric constant: 6.5, X-direction dielectric loss tangent: 0.01, and Y-direction dielectric loss tangent: 0.01, without allowing air to enter the glass sheet. The antenna circuit board was disposed in an area 2 cm to 7 cm inward from the longitudinal end of the glass sheet. By heating these for 1 hour in a hot air dryer at 50°C, glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna system was obtained in which an antenna circuit board with a protective glass plate was arranged on a part of the glass. No displacement of the film was observed even when a shear force was applied to the obtained antenna system. Furthermore, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, high frequency waves incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0210] [Example 18] <Fabrication of antenna system> Except for using dibutoxyethyl adipate instead of triethylene glycol-di-(2-ethylhexanoate), the same procedure as in Example 17 was used to obtain an antenna system in which glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was disposed on a part of the glass. No displacement of the film was observed even when a shear force was applied to the obtained antenna system. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0211] [Example 19] <Fabrication of antenna system> In the same manner as in Example 17, except that the heating in the hot air dryer was changed to 30°C and 24 hours, glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was arranged on a part of the glass to obtain an antenna system. Even when a shear force was applied to the obtained antenna system, no deviation of the film was observed. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0212] [Example 20] <Fabrication of antenna system> Except for changing the heating temperature in the hot air dryer to 30°C, the same procedure as in Example 18 was used to obtain an antenna system in which glass (first glass layer) / polyvinyl acetal resin film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer) / polyvinyl acetal resin film (low dielectric layer) / thin glass (protective layer) were laminated in this order, and an antenna circuit board with a protective glass plate was disposed on a part of the glass. No film shift was observed even when a shear force was applied to the obtained antenna system. In addition, in the obtained antenna system, since the low dielectric layer has a dielectric constant smaller than that of the glass, the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0213] [Example 21] <Fabrication of antenna circuit board> Copper foil (Fukuda Metal Foil and Powder Co., Ltd., electrolytic copper foil "H9A", thickness 12 μm) was superimposed on both sides of a thermoplastic liquid crystal polymer film (Kuraray Co., Ltd., Vecstar (registered trademark), thickness 50 μm, dielectric constant in X direction: 3.4, dielectric constant in Y direction: 3.4, dielectric loss tangent in X direction: 0.002, dielectric loss tangent in Y direction: 0.002), and a vacuum hot press was used to set the heating plate to 290 ° C. and press the film under a pressure of 4 MPa for 15 minutes to produce a copper-clad laminate having a copper foil / thermoplastic liquid crystal polymer film / copper foil configuration. A part of the copper foil on one side of the obtained copper-clad laminate was removed with an etching solution to form a circuit, and this operation was repeated to produce an antenna circuit board (length 3 cm, width 3 cm) having a thickness of 400 μm.

[0214] <Fabrication of antenna system> A polyvinyl acetal film (Kuraray Co., Ltd., V200KE, thickness 700 μm, dielectric constant in X direction: 2.7, dielectric constant in Y direction: 2.7, dielectric dissipation factor in X direction: 0.02, dielectric dissipation factor in Y direction: 0.02) measuring 3 cm in length and 3 cm in width was placed on a piece of glass measuring 20 cm in length, 10 cm in width, and 3.5 mm in thickness, with a dielectric constant in X direction: 6.5, a dielectric constant in Y direction: 6.5, a dielectric dissipation factor in X direction: 0.01, and a dielectric dissipation factor in Y direction: 0.01, on which the upper end of the film was 2 cm below (inward) from the upper end of the glass in the vertical direction and the center of the film in the horizontal direction overlapped with the center of the glass in the horizontal direction. The antenna circuit board prepared above was placed on top of the film so that the surface having the circuit was in contact with the polyvinyl acetal film. Then, while the position of the antenna circuit board is held, the glass is placed in a vacuum bag, and treated at 100°C under reduced pressure for 30 minutes. After cooling, the reduced pressure is released, and the antenna circuit board is pre-laminated to the glass. Then, this is placed in an autoclave and treated at 140°C and 1.2MPa for 30 minutes, to obtain an antenna system in which the antenna circuit board is disposed on a part of the glass in the following order: glass (first glass layer) / polyvinyl acetal film (low dielectric layer) / circuit (circuit layer) / antenna circuit board inner layer (multilayer board with thermoplastic liquid crystal polymer film as an insulating layer) / copper foil (conductor layer). In the obtained antenna system, the thickness df of the low dielectric layer is 700μm, and the range of λ / 4×n±0.050mm (n=2) is satisfied for the high frequency of the target wavelength λ (1.47mm).

[0215] When a high frequency wave with a wavelength λ is incident on the glass side of the obtained antenna system, the polyvinyl acetal film has a dielectric constant smaller than that of the glass and falls within the range satisfying the above formula (I), and therefore the high frequency wave incident on the glass can pass through the polyvinyl acetal layer, which is a low dielectric layer, and reach the antenna circuit board. In addition, the thickness of the low dielectric layer satisfies the range of λ / 4×n±0.050 mm, allowing high frequency waves to reach the antenna circuit board efficiently.

[0216] [Example 22] In the case where an antenna system is produced in the same manner as in Example 21 except that multiple polyvinyl acetal films [MFR (190°C, 2.16 kg) 0.75 g / 10 min, thickness 50 μm, dielectric constant in X direction: 2.5, dielectric constant in Y direction: 2.5, dielectric loss tangent in X direction: 0.01, dielectric loss tangent in Y direction: 0.01] are stacked instead of the low dielectric layer used in Example 21, the low dielectric layer has a dielectric constant smaller than that of glass, similarly to Example 21, and therefore the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0217] [Example 23] In the case where an antenna system is produced in the same manner as in Example 21 except that an ionomer film (manufactured by Kuraray Co., Ltd., SGR5000, thickness 1000 μm, dielectric constant in X direction: 2.2, dielectric constant in Y direction: 2.2, dielectric loss tangent in X direction: 0.002, dielectric loss tangent in Y direction: 0.002) is used instead of the low dielectric layer used in Example 21, the low dielectric layer has a dielectric constant smaller than that of glass, similarly to Example 21, and therefore the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board.

[0218] [Example 24] In place of the thermoplastic liquid crystal polymer film of the antenna circuit board used in Example 21, a polyimide film (manufactured by Toray DuPont Co., Ltd., Kapton 300H, thickness 75 μm, dielectric constant in X direction: 3.3, dielectric constant in Y direction: 3.3, dielectric loss tangent in X direction: 0.007, dielectric loss tangent in Y direction: 0.007) is used, and bonding within the antenna circuit board is performed using a low dielectric adhesive SAFY (dielectric constant: 3, dielectric loss tangent: 0.005) manufactured by Nikkan Industries Co., Ltd. When an antenna system is produced in the same manner as in Example 21, the low dielectric layer has a dielectric constant smaller than that of glass, as in Example 21, and therefore the high frequency wave incident on the glass can penetrate the low dielectric layer and reach the antenna circuit board.

[0219] [Example 25] In the case where an antenna system is produced in the same manner as in Example 24, except that a polyimide film (Apical NPI, manufactured by Kaneka Corporation, thickness 50 μm, dielectric constant in X direction: 3.4, dielectric constant in Y direction: 3.4, dielectric loss tangent in X direction: 0.004, dielectric loss tangent in Y direction: 0.004) is used instead of the polyimide film used in Example 24, the low dielectric layer has a dielectric constant smaller than that of the glass, as in Example 21, and therefore the high frequency wave incident on the glass can pass through the low dielectric layer and reach the antenna circuit board. [Industrial Applicability]

[0220] The antenna system of the present invention suppresses attenuation of high frequencies, improves the transmission characteristics of the antenna circuit board for high frequencies, and can exchange a large amount of information, and therefore can be usefully used as an antenna system for vehicles such as so-called connected cars for automatic driving and constant communication by on-board devices, an antenna system for small cell base stations by installing it on windows and walls of buildings, various civil engineering structures (railroad facilities, road facilities, energy facilities, dams and river facilities, water supply and sewerage facilities, airport facilities), etc. For example, the antenna system of the present invention can be used by forming the window glass of a vehicle or building, or by attaching it to a vehicle or building.

[0221] Although the preferred embodiment of the present invention has been described above with reference to the drawings, a person skilled in the art will easily imagine various changes and modifications within the obvious scope upon reading the specification. Therefore, such changes and modifications are interpreted as falling within the scope of the invention as defined by the claims. [Explanation of symbols]

[0222] 100, 200, 300, 400, 500, 600… Antenna Systems 101, 201, 301, 401, 501, 601…First glass layer 202, 302, 502, 602…Second glass layer 103, 203, 303, 403...Low dielectric layer 503a, 603a...first low dielectric layer 503b, 603b...Second low dielectric layer 104...Circuit layer 105...High frequency insulation layer 106...Conductor layer 107...Antenna circuit board 308...adhesive layer 408a, 408b…Fixing means 409…Adherent

Claims

1. a first glass layer that is transparent to radio frequency waves; a low dielectric layer having a dielectric constant lower than that of the first glass layer, adjacent to the first glass layer, and transmitting high frequency waves incident from the first glass layer; an antenna circuit board adjacent to the low dielectric layer and configured to receive high frequency waves incident from the low dielectric layer; 1. An antenna system for use at frequencies above 1 GHz, comprising: The antenna circuit board includes at least one high-frequency insulating layer and at least one circuit layer. the at least one circuit layer is disposed on a surface of the high frequency insulating layer and includes a circuit layer adjacent to the low dielectric layer; Antenna system.

2. 10. The antenna system of claim 1, wherein the high frequency insulating layer is made of a thermoplastic liquid crystal polymer or a polyimide.

3. 3. The antenna system according to claim 1, wherein the dielectric constant εg of the first glass layer is 5.5 to 7.5, and the dielectric constant εf of the low dielectric layer is 2.0 to 4.0, as dielectric constants in both one direction in a plane and a direction perpendicular thereto, measured at a frequency of 28 GHz.

4. 4. The antenna system according to claim 1, wherein the dielectric loss tangent tan δg of the first glass layer is 0.05 or less, and the dielectric loss tangent tan δf of the low dielectric layer is 0.05 or less, as dielectric loss tangents in both one direction in a plane and in a direction perpendicular thereto, measured at a frequency of 28 GHz.

5. 5. The antenna system according to claim 1, wherein the low dielectric layer is made of at least one selected from the group consisting of polyvinyl acetal resin, olefin-vinyl carboxylate copolymer resin, ionomer resin, and acrylic resin.

6. 6. The antenna system according to claim 1, wherein the high-frequency insulating layer has a dielectric constant εp of 2.0 to 4.0, measured at a frequency of 28 GHz in both one direction in a plane and in a direction perpendicular thereto.

7. 7. The antenna system according to claim 1, wherein the dielectric loss tangent tan δp of the high frequency insulating layer is 0.010 or less as a dielectric loss tangent in both one direction in a plane and in a direction perpendicular thereto, measured at a frequency of 28 GHz.

8. 8. The antenna system according to claim 1, wherein the dielectric constant εf of the low dielectric layer and the dielectric constant εp of the high frequency insulating layer are εf / εp=30 / 70 to 60 / 40.

9. 9. An antenna system according to any one of claims 1 to 8, wherein the low dielectric layer has a thickness of λ / 4×n±0.050 mm, where λ is the wavelength of the radio frequency and n is an integer.

10. 10. The antenna system according to claim 1, wherein the first glass layer is made of at least one glass selected from the group consisting of soda-lime glass, borate glass, borosilicate glass, aluminosilicate glass, quartz glass, alkali-free glass, and low-alkali glass.

11. 11. The antenna system according to claim 1, further comprising a second glass layer, and at least a low dielectric layer and an antenna circuit board are disposed between the first glass layer and the second glass layer.

12. An antenna system according to any one of the preceding claims, comprising a glazing on a vehicle or building.

13. 12. An antenna system according to any one of claims 1 to 11, for receiving radio waves while attached to a vehicle, a building or a civil structure.

14. A laminate for use in the antenna system according to any one of claims 1 to 13, comprising an antenna circuit board and a low dielectric layer adjacent to the antenna circuit board, At least one high frequency insulating layer and at least one circuit layer are provided, the at least one circuit layer is disposed on a surface of the high frequency insulating layer and includes a circuit layer adjacent to the low dielectric layer; Laminate.

Citation Information

Patent Citations

  • Vehicle antenna

    JP2007053505A

  • Antenna array device and abnormal tissue detector

    JP2014131199A

  • Laminated glass plate with heating electrode, and vehicle

    JP2017183063A

  • Antenna unit, window glass equipped with antenna unit, and matching body

    WO2019177144A1